Middle-late Devonian warming and land plant evolution drive changes in silicate weathering: A new 87Sr/86Sr conodont record paired with δ18O - Teresa D. Avila; Matthew R. Saltzman; Michael M. Joachimski; Elizabeth M. Griffith; Benjamin J.W. Mills (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Connecting ambient toxicity testing with community-level responses of benthic macroinvertebrates in an impacted stream in East Tennessee, USA - Louise M. Stevenson; Paul G. Matson; Peyton C. Marcum; Nikki J. Jones; Scott C. Brooks; Trystan Bordeau; Allison M. Fortner; Natalie A. Griffiths; Christopher R. DeRolph; R. Trent Jett; Michael W. Jones; Peijia Ku; et al. (Journal of Environmental Management, 2026)

The Triassic Mercia Mudstone Group: Sealing the UK's net zero future - Jonathon A. McEvoy; Richard H. Worden; Joshua Griffiths; Nicholas T. Smith; Daniel R. Faulkner; Samuel T.J. Jones; Holly J. Mills; Kevin G. Taylor (Earth-Science Reviews, 2026)

Pathways and processes controlling the distribution of anthropogenic lead in the interior of the Southern Ocean - Alex Griffiths; Yee-Lap Leung; Andrew R. Bowie; Melanie East; Mark Rehkämper; Tina van de Flierdt (Geochimica et Cosmochimica Acta, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Oxidative stabilization of high-PUFA biodiesel feedstocks using squalene: A multi-scale chemical and thermal analysis - V. Sharma; G. Griffiths; N. Collins; Abul K. Hossain; R. Sodré; D. Ganesh; R. Vinu; K. Anand (Bioresource Technology Reports, 2026)

Effects of maternal arsenic exposure on birth outcomes using harmonized data across three birth cohorts - Zlatan Feric; Daniel Beene; Antonio J. Signes-Pastor; Deborah J. Watkins; Griffith Gao; Margaret R. Karagas; Debra A. MacKenzie; David R. Kaeli; Justin Manjourides (Toxicology and Environmental Health Sciences, 2026)
Objectives To assess the association between urinary arsenic concentrations and birth outcomes by harmonizing data from three independent birth cohorts. Methods We harmonized and analyzed data from the Navajo Birth Cohort Study (NBCS), the New Hampshire Birth Cohort Study (NHBCS), and the PROTECT Center study based on Puerto Rico. Birth outcomes of interest included birth weight, head circumference, birth length, gestational age at delivery, incidence of preterm birth, and size for gestational age. Urinary arsenic concentrations were used as the primary exposure metric. Harmonization involved aligning variable formats, adjusting for differences in laboratory methods, and excluding incompatible covariates, such as income and race. Results Harmonization increased the total sample size ( N = 3222) across cohorts. However, pooled analyses did not consistently demonstrate increased statistical power. Effect estimates for arsenic exposure were attenuated in some cases, and confidence intervals remained wide or even expanded relative to individual cohort analyses. Differences in biospecimen collection and laboratory assay methods required cohort-specific adjustments. Due to missing arsenic speciation data, the PROTECT cohort was excluded from two exposure models. Variability across cohorts limited the interpretability and precision of pooled estimates despite harmonization efforts. Conclusions While harmonizing data across multiple cohorts increased the sample size, it did not necessarily enhance statistical power or strengthen observed associations. Differences in data collection, laboratory methods, and available covariates posed significant challenges. These findings underscore the need for caution when interpreting pooled results from heterogeneous sources and highlight the importance of prospective planning for data harmonization in multi-cohort studies.

Nitrogen cycling in a high-nutrient tidal river revealed through high-resolution sampling and nitrate isotope mixing models - Josh Guyat; Douglas R. Tait; James Z. Sippo; Benjamin T. Stewart; Angus Ferguson; James A. Padilla-Montalvo; Christopher Ralph; Jenny Rogers; Merran Griffith; Dirk V. Erler; Michael Ingram; Damien T. Maher (Geochimica et Cosmochimica Acta, 2026)

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Biochar reshapes soil bacterial community composition and survival strategies: a meta-analysis revealing trade-offs between microbial stability and functional complexity - Jianwei Li; Jeewani H. Peduruhewa; Robert W. Brown; David R. Chadwick; Robert I. Griffiths; Haoran Fu; Hongfeng Bian; LianXi Sheng; Qinqxu Ma; Davey L. Jones (Biology and Fertility of Soils, 2026)
As a promising strategy for improving soil health and mitigating climate change, biochar has received increasing attention in recent years. However, findings regarding its microbial effects are often context-dependent, and the complex impacts of biochar on soil microbial communities remain inadequately understood. Here, we integrated 843 samples of 16 S rRNA sequencing data from 24 independent studies, utilizing machine learning and co-occurrence network analysis to evaluate general patterns and mechanisms by which biochar alters bacteria community composition and survival strategies. Overall, biochar significantly increased soil organic C, total N, pH, and reduced bulk density, which in turn affected microbial communities. While biochar addition did not notably alter bacterial α-diversity (Shannon index or species richness), it significantly changed β-diversity, indicating that biochar addition altered microbial community composition. Biochar changed community composition and survival strategies by reducing the oligotroph/copiotroph ratio, favouring copiotrophs groups (e.g., Bacteroidota). K -strategists (e.g., Planctomycetota) were reduced by biochar, potentially due to increased nutrient availability and increased competition. Model selection analysis identified that soil physicochemical properties were key drivers of α-diversity, while climate variables were the main factors influencing β-diversity. Biochar properties represented key factors influencing changes in microbial survival strategy. Machine learning identified 138 biomarker genera, with biochar-treated soils showing an increase in Pseudomonadota. Co-occurrence network analysis indicated that biochar increased microbial stability, but reduced network complexity, suggesting a trade-off between resilience and functional redundancy following biochar addition. These findings provide new insights into how biochar influences the composition and ecological functions of soil bacterial communities and offer theoretical support for its scientific application in sustainable soil management.

Quantifying changes in central Vietnam rainfall amount since the Late Pleistocene - Elizabeth W. Patterson; Alliya A. Akhtar; Michael L. Griffiths; David McGee; Quốc Đỗ-Trọng; Annabel Wolf; John A. Higgins; Stefania Gili; Mùi X. Trần; Hùng Q. Nguyễn; Trí H. Đinh; Thành N. Bùi; et al. (Earth and Planetary Science Letters, 2026)

Overlooked seasonal groundwater nutrient fluxes rival anthropogenic point sources across a variable land‐use tidal river - James A. Padilla‐Montalvo; Douglas R. Tait; Michael J. Reading; Benjamin T. Stewart; Angus Ferguson; Iremar Fernandez‐Vazquez; James Z. Sippo; Shivanesh Rao; Mitch Call; Christopher Ralph; Josh Guyat; Jenny Rogers; et al. (Limnology and Oceanography, 2025)
Understanding groundwater–surface water connectivity in tidal freshwater zones is essential for managing ecosystems within the riverine–estuarine continuum. Groundwater discharge is a key source of dissolved nutrient loads that can lead to eutrophication, deoxygenation, and other ecosystem imbalances in coastal environments. However, groundwater is an often‐overlooked nutrient delivery pathway, with limited studies quantifying groundwater inputs into freshwater transitional zones. Here, we quantify groundwater discharge and its associated nutrient fluxes along a ≈ 75 km section of a tidal freshwater zone within the Hawkesbury–Nepean River (New South Wales, Australia), which is surrounded by multiple land uses. High‐resolution timeseries and spatial surveys were employed over three hydrologically distinct seasons using the naturally occurring radioisotope tracer, radon. Survey results revealed decreasing surface water radon activity and nutrients toward the downstream estuarine boundary. Estimated groundwater discharge rates were highest in the upstream reaches (6.0–12.5 cm d −1 ), regardless of seasonal hydrological dynamics, and decreased downstream, aligning with a reduction in irrigation‐dependent agricultural practices and a change in adjacent catchment morphology. During the dry period, groundwater accounted for up to ≈ 68% of upstream river inputs. Groundwater discharge was also a major source of dissolved inorganic nitrogen, contributing between 0.8 and 1.1 times the inputs from local wastewater treatment plants, and up to 15 times more phosphate than upstream river sources. These findings highlight the role of groundwater discharge as a nutrient driver for tidal freshwater zones, which could have significant implications for future management strategies in these environments.

Preliminary insights into manta ray (Mobula alfredi and M. birostris) population demographics and distribution in South Africa - M. Carpenter; N. Cullain; R. Daly; G. Smith; M. Dicken; V. Dames; C. L. Griffiths; A. D. Marshall (Environmental Biology of Fishes, 2025)
Both the reef manta ray, Mobula alfredi and oceanic manta ray M. birostris , are repeatedly observed in South Africa, yet little is known about the distributions of either species. In this study, we collated citizen science observations since 2003 to reveal six areas in the KwaZulu-Natal (KZN) and Eastern Cape provinces, where manta rays have been sighted across multiple years. Using their unique ventral spot patterning, 184 individuals were photo-identified, comprising 139 M. alfredi and 45 M. birostris . Most of the photo-identified M. alfredi individuals were encountered in the iSimangaliso Wetland Park (IWP) in KZN (89%; n = 119) and for M. birostris , Aliwal Shoal (48%; n = 22). We identified 32 new transboundary records of 28 M. alfredi also photographed in the Inhambane Province, Mozambique, demonstrating connectivity, specifically to Závora ( n = 27). One M. alfredi individual traveled multiple times between the IWP and Závora, Mozambique, totaling 1305 km, and another individual traveled from the Pondoland MPA to the IWP in South Africa, a distance of over 600 km. Further, we extend the southern range for M. alfredi in Africa by over 500 km from Mdumbi Beach to Port Ngqura, Eastern Cape. These collective findings represent South Africa’s first in-water assessment of manta ray aggregations, showing the IWP in particular to be a critical habitat for M. alfredi . Further, the movements documented here suggest the M. alfredi population in southern Africa to be one of the most mobile globally. We hope the baseline data provided here will drive increased research and transboundary management for M. alfredi and M. birostris along the KZN and Eastern Cape coastlines.

Biodegradable mulch films exhibit slower-than-expected degradation with negligible effects on soil microbial communities - Martine Graf; Estelle Choiselat; Michaela K. Reay; Rafael Bargiela; Athanasios Dimitriou; Qiuyun Liu; Robert M. Elias; Peter N. Golyshin; Robert Griffiths; David R. Chadwick; Davey L. Jones (Journal of Hazardous Materials, 2025)

High-resolution record of global cooling during a large Mississippian positive carbon isotope excursion - Noah T. Anderson; Kristin D. Bergmann; Matthew G. Braun; Elizabeth M. Griffith; Matthew R. Saltzman (Earth and Planetary Science Letters, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Maternal Electronic Cigarette Inhalation Exposure During Gestation: Impacts on Prolactin and Xanthine Oxidase - Julie A. Griffith; Kallie J. Schafner; Krista L. Garner; Evan DeVallance; Sara E. Lewis; Timothy R. Nurkiewicz; Eric E. Kelley; Brooke A. Maxwell; William T. Goldsmith; Elizabeth C. Bowdridge (Cardiovascular Toxicology, 2025)

Environmental risk factors for all-cause dementia, Alzheimer's disease dementia, vascular dementia, and mild cognitive impairment: An umbrella review and meta-analysis - Aaron Jones; Muhammad Usman Ali; Alexandra Mayhew; Komal Aryal; Rebecca H. Correia; Darly Dash; Derek R. Manis; Atiya Rehman; Megan E. O'Connell; Vanessa Taler; Andrew P. Costa; David B. Hogan; et al. (Environmental Research, 2025)

John Raven, FRS, FRSE: a truly great innovator in plant physiology, photosynthesis and much more - A. W. D. Larkum; P. G. Falkowski; Dianne Edwards; C. B. Osmond; H. Lambers; P. Sanchez-Baracaldo; R. J. Ritchie; J. W. Runcie; P. J. Ralph; M. Westoby; S. Maberly; H. Griffiths; et al. (Photosynthesis Research, 2025)
This is a tribute to a truly inspirational plant biologist, Prof. John A. Raven, FRS, FRSE (25th June 1941– 23rd May 2024), who died at the age of 82. He was a leader in the field of evolution and physiology of algae and land plants. His research touched on many areas including photosynthesis, ion transport, carbon utilisation, mineral use, such as silicon, iron and molybdenum, the evolution of phytoplankton, the evolution of root systems, the impact of global change, especially on the acidification of the oceans, carbon gain and water use in early land plants, and ways of detecting extraterrestrial photosynthesis. Beginning his research career in the Botany School, University of Cambridge, John studied ion uptake in a giant algal cell. This was at the time of great strides brought about by Peter Mitchell (1920–1992) in elucidating the role of energy generation in mitochondria and chloroplasts and the coupling of ion transport systems to energy generation. With Enid MacRobbie and Andrew Smith, John pioneered early work on the involvement of ion transport in the growth and metabolism of plant cells.On leaving Cambridge John took up a lectureship at the University of Dundee in 1971, where he was still attached upon his death. His primary focus over the years, with one of us (Paul Falkowski), was on phytoplankton, the photosynthetic microalgae of the oceans. Still, his publication list of 5 books and over 600 scientific papers spans a very broad range. The many highly cited papers (see Table 1) attest to an outstanding innovator, who influenced a multitude of students and coworkers and a very wide readership worldwide. At the personal level, John Raven was a wonderful human being; he had an extraordinary memory, dredging up facts and little-known scientific papers, like a scientific magician, but at the same time making humorous jokes and involving his colleagues in fun and sympathetic appreciation. Table 1 Ten best cited articles (from google scholar) Citations Date Aquatic Photosynthesis, 3rd EditionP.G. Falkowski & J.A. RavenPrinceton University Press, 2013 3854 2013 The evolution of modern eukaryotic phytoplanktonP.G. Falkowski, M.E. Katz, A.H. Knoll, A. Quigg, J.A. Raven, et alScience 305 , 354–360 1790 2004 C O 2 concentrating mechanisms in algae:mechanisms, environmental modulation, and evolutionM. Giordano, J. Beardall & J.A. RavenAnnu. Rev. Plant Biol. 56 (1), 99–131 1648 2005 Algae as nutritional food sources: revisiting our understandingM.L. Wells, P. Potin, J.S. Craigie, J.A. Raven, S.S. Merchant, et alJournal of applied phycology 29 , 949–982 1527 2017 Plant Nutrient acquisition strategies change with soil ageH. Lambers, J.A. Raven, G.R. Shaver & S.E. SmithTrends in ecology & evolution 23 , 95–103 1488 2008 Ocean acidification due to increasing atmospheric carbon dioxideJ. Raven, K. Caldeira, H. Elderfield, O. Hoegh-Guldberg, P. Liss, et alThe Royal Society, Policy Document, June 2005 1470 2005 Phytoplankton in a changing world: cell size and elemental stoichiometryZ.V. Finkel, J. Beardall, K.J. Flynn, A. Quigg, T.A.V. Rees & J.A. RavenJournal of plankton research 32 , 119–137 1198 2010 Opportunities for improving phosphorus efficiency in crop plantsE.J. Veneklaas, H. Lambers, J. Bragg, P.M. Finnegan, C.E. Lovelock, et alNew phytologist 195 , 306–320 951 2012 Adaptation of unicellular algae to irradiance: an analysis of strategiesK. Richardson, J. Beardall & J.A. RavenNew Phytologist 93 , 157–191 914 1983 N itrogen assimilation and transport in vascular land plants in relation to Intracellular pH regulationJ.A. Raven & F.A. SmithNew Phytologist 76 , 415–431 893 1976 Temperature and algal growth J.A. Raven & R.J. GeiderNew phytologist 110 , 441–461 867 1988 The role of trace metals in photosynthetic electron transport in O 2 -evolving organismsJ.A. Raven, M.C.W. Evans & R.E. KorbPhotosynthesis Research 60 , 111–150 840 1999

A summary and critique of the various spectrophotometric methods used to quantify C-phycocyanin concentration - Eric J. R. Payne; Melinda Griffiths; Susan T. L. Harrison; Marijke A. Fagan-Endres (Journal of Applied Phycology, 2025)
A wide range of research has been conducted on various applications and purification methods of C-phycocyanin (C-PC). In the published literature, there has not been consistency in the methods used to determine the concentration of C-PC within solution. This is an important characteristic to accurately determine the efficiency of a C-PC purification process and the quality of a final C-PC product. This brief report aims to critically evaluate the equations used to calculate C-PC concentration from spectrophotometric readings published in literature by discussing the logic behind the different coefficients and wavelengths used as well as by comparing the concentrations obtained for a Spirulina derived C-PC sample using the various equations. Some of the equations investigated, predominantly those which only differed slightly in the measured wavelengths, generated similar concentration results. However, these were based on work initially done on a specific cyanobacterium, Fremyella diplosiphon (Bennett and Bogorad 1973). Equations generated using other cyanobacteria extracts or even species of macroalgae generated markedly different C-PC concentrations. When these equations have been used in literature, there is often no distinction made as to whether the algal species being investigated is the same as the one used to develop the equation originally. The goal of this investigation was therefore to highlight this issue so that a more consistent and microalgal-species-appropriate approach can be used in the future for quantifying C-PC concentration in solution.

Exploring the activated charcoal adsorption column to improve cosmetic grade C-phycocyanin purification from Spirulina - Eric J. R. Payne; Melinda Griffiths; Susan T. L. Harrison; Marijke A. Fagan-Endres (Journal of Applied Phycology, 2025)
This study investigates the effectiveness of activated charcoal, a common adsorbent, in various packed column configurations in the context of a process to purify C-phycocyanin (C-PC) from Spirulina . The adsorption column performance is considered in isolation and as part of purification trains, which include chitosan treatment and ammonium sulfate precipitation. Operating parameters of interest included activated charcoal particle size, solution retention time in the column and concentration of the Spirulina crude extract used. The feed was a low purity crude extract and the final target was cosmetic grade C-PC (purity > 1.5). A slower column feed flowrate and smaller activated charcoal particle size were shown to improve the degree of C-PC purification via adsorption. Variation of the crude extract concentration did not have a significant effect. In all cases, high C-PC recoveries over the column were achieved. However, use of a single activated charcoal adsorption column was not able to purify the C-PC to cosmetic grade. Cosmetic grade purity (of between 1.68 ± 0.18 and 2.61 ± 0.44) was reached by coupling the column with chitosan treatment and ammonium sulfate precipitation when using a lower feed concentration of 2.60 ± 0.07 mg C-PC mL −1 . A higher concentration feed could not be purified to cosmetic grade within this investigation, confirming that feed concentration affects the efficiency of the activated charcoal column in combination with the other downstream process steps. The overall process had better yields and was able to accommodate a higher concentration of C-PC than reported in literature.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Natural history traits influence winners and losers for herpetological communities in disturbed tropical habitats - Rowland K. Griffin; Todd R. Lewis; Joseph Tzanopoulos; Richard A. Griffiths (Oecologia, 2025)
Habitat alteration can lead to a few ‘winning’ species outcompeting many ‘losing’ species, an effect commonly termed as ‘Winner-Loser-Replacements’ or WLRs. This can lead to homogenisation of species assemblages at phylogenetic and functional levels. Most previous studies analyse responses of species abundance without considering natural history traits associated with those species. This study uses fourth corner modelling techniques to investigate the interaction between ecological data and natural history trait information using a herpetofaunal assemblage that includes 19 species of amphibians, 28 snakes, and 20 lizards, in Parque Nacional Laguna del Tigre, Guatemala. A total of 120 transects were surveyed using Visual Encounter Surveys, comprising 18 in disturbed habitat, 66 in forest habitat, and 36 in edge habitat respectively. Overall, greater diversity of ecological traits was revealed in forest and edge habitats compared to disturbed habitats at the forest edge close to agricultural land. Models revealed that for amphibians ( Hypopachus variolosus and Incilius valliceps ) and snakes ( Coniophanes schmidtii and Leptodeira septentrionalis ), association with bare ground, and in the case of amphibians, leaf litter, predicts species persistence in disturbed habitats. Continued forest fragmentation in the region will result in increased edge effects, and a greater proportion of forest remaining in an early successional state, leading to a highly reduced, homogenized, amphibian and reptile assemblage. Using such models for community assemblages of animals to reveal the identity of WLR patterns in forests with continued fragmentation is a useful tool to reveal which species are at risk of impact before habitats become degraded.

Prenatal exposure to environmental bisphenols over time and their association with childhood asthma, allergic rhinitis and atopic dermatitis in the ECHO consortium - Rachel L. Miller; Yuyan Wang; Jenny Aalborg; Akram N. Alshawabkeh; Deborah H. Bennett; Carrie V. Breton; Jessie P. Buckley; Dana Dabelea; Anne L. Dunlop; Assiamira Ferrara; Griffith Gao; Abigail Gaylord; et al. (Environmental Pollution, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Genetic analysis of grain protein content and deviation in wheat - Rohan Richard; Alison Lovegrove; Paola Tosi; Richard Casebow; Mervin Poole; Luzie U. Wingen; Simon Griffiths; Peter R. Shewry (Journal of Cereal Science, 2025)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Calcium isotope constraints on a Middle Ordovician carbon isotope excursion - Y. Datu Adiatma; Matthew R. Saltzman; Elizabeth M. Griffith (Earth and Planetary Science Letters, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Genomic patterns of native palms from the Leeward Antilles confirm single-island endemism and guide conservation priorities - James A. R. Clugston; Quirijn Coolen; Erik Houtepen; André S. J. van Proosdij; Ayress D. Grinage; M. Patrick Griffith (Conservation Genetics, 2024)
Systematic study of the palm (Arecaceae) flora from the Leeward Antilles marked both Sabal antillensis and Sabal lougheediana as endemic to Curaçao and Bonaire respectively. Although both species are emergent, obvious and charismatic elements of the Antillean flora, they were only described within the last decade. Sabal lougheediana is in demographic crisis as a result of constant ungulate pressure prohibiting seedling establishment, while S. antillensis is thriving as a result of careful management. Given the surprisingly recent discovery of these two species, and the severity of the conservation concern, genomic data can help inform whether these taxa are in fact well-circumscribed species, and help to guide further conservation actions. To investigate genomic diversity, we employed RADSeq data from samples throughout the range of both species. Results show significant genetic distance and fixation between the two taxa as currently circumscribed, as well as reduced genetic diversity and increased inbreeding in both species. Multivariate analysis of genetic distance and Bayesian clustering analysis both show clear and significant separation of the two taxa. Parallel assay of ex situ collections informs how future development of germplasm reserves can help support conservation of both species. We provide recommendations to help conserve these two unique and distinct species.

Cannabis use in Parkinson’s disease: Patient access to medical cannabis and physician perspective on product safety - Symone T. Griffith; Kendra D. Conrow; Michael Go; Mindy L. McEntee; Raminta Daniulaityte; Majia H. Nadesan; Mathew R. Swinburne; Holly A. Shill; Maxwell C.K. Leung (NeuroToxicology, 2024)

Behavior, site use and demographics of shortfin devil rays, Mobula kuhlii, at a newly-discovered cleaning area in South Africa - M. M. Carpenter; R. J. Y. Perryman; A. D. Marshall; C. L. Griffiths (Marine Biology, 2024)
Many shark and ray species show affinity to specific sites, making these areas critical for their survival. These include cleaning stations: locations on reefs where cleaner fish remove parasites and clean wounds, which is important for maintaining health. Cleaning stations also function as social gathering sites, or resting points, where courtship and mating can occur. In this study, we identify an aggregation site for the shortfin devil ray, Mobula kuhlii (Family Mobulidae) within the Aliwal Shoal Marine Protected Area in KwaZulu-Natal (KZN), South Africa, and document their behavior. Remote underwater video was used to collect footage of M. kuhlii being cleaned by blue streak cleaner wrasse, Labroides dimidiatus . Generalized additive models (GAMs) were used to assess environmental predictors of M. kuhlii presence on Aliwal Shoal. Mixed models were used to assess the same environmental predictors and their correlation with mean M. kuhlii cleaning duration and number of L. dimidiatus bites per second at the identified cleaning station site. M. kuhlii were present in 56% of observation days, with group numbers up to > 150 individuals. Sea surface temperature was a significant predictor for M. kuhlii presence, while a north to south current was significantly associated with longer mean cleaning durations. These results support findings of mobulid studies in KZN that show increased habitat use during summer temperatures (24–25 °C) and suggest these sites to be important for individual health and social interaction. We hope these findings can be used for development of location-specific management plans to safeguard this Endangered species.

Density data for L ake E rie benthic invertebrate assemblages from 1930 to 2019 - Lyubov E. Burlakova; Alexander Y. Karatayev; Allison R. Hrycik; Susan E. Daniel; Knut Mehler; Elizabeth K. Hinchey; Ronald Dermott; Ronald Griffiths; Lillian E. Denecke (Ecology, 2024)
Benthic invertebrates are important trophic links in food webs and useful bioindicators of environmental conditions, but long‐term benthic organism abundance data across broad geographic areas are rare and historic datasets are often not readily accessible. This dataset provides densities of benthic macroinvertebrates collected from 1930 to 2019 during surveys in Lake Erie, a Laurentian Great Lake. The surveys were funded by the governments of the United States and Canada to investigate the status and changes in the benthic community. From the total of 21 lake‐wide and basin‐wide benthic surveys conducted in Lake Erie from 1929 to 2019, we were able to acquire data for 17 surveys, including species‐level data for 10 surveys and data by higher taxonomic groups for seven surveys. Our amassed Lake Erie dataset includes data from 11 surveys (including five with species‐level data) conducted in the western basin in 1930–2019, seven surveys (six with species‐level data) in the central basin, and eight surveys (seven with species‐level data) in the eastern basin (1973–2019). This Lake Erie dataset represents the most extensive temporal dataset of benthic invertebrates available for any of the Laurentian Great Lakes. Benthic samples were collected using Ponar or Shipek bottom dredges and taxa densities were calculated as individuals per square meter using the area of the dredge. Density data are provided for taxa in the Annelida, Arthropoda, Mollusca, Cnidaria, Nemertea, and Platyhelminthes phyla. Current taxonomy was used for most groups but, in a few cases, older taxonomic names were used for consistency with historical data. Analysis of this dataset indicates that eutrophication, water quality improvement, and dreissenid introduction were the major drivers of changes in the benthic community in the western basin, while hypoxia was a major factor in the central basin, and dreissenid introduction was the most important driver in the eastern basin. Considering the rarity of high taxonomic resolution long‐term benthic data for lake ecosystems, this dataset could be useful to explore broader aspects of ecological theory, including effects of eutrophication, hypoxia, invasive species, and other factors on community organization, phylogenetic and functional diversity, and spatial and temporal scales of variation in community structure. In addition, the dataset could be useful for studies on individual species, including abundance and distribution, species co‐occurrence, and how the patterns of dominance and rarity change over space and time. Use of this dataset for academic or educational purposes is encouraged as long as this data paper is properly cited.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

The underwater soundscape of the North Sea - F. Basan; J.-G. Fischer; R. Putland; J. Brinkkemper; C.A.F. de Jong; B. Binnerts; A. Norro; D. Kühnel; L.-A. Ødegaard; M. Andersson; E. Lalander; J. Tougaard; et al. (Marine Pollution Bulletin, 2024)

Remedial effectiveness of a pond biomanipulation: Habitat value and concentrations of polychlorinated biphenyls in fish - Rebecca A. Efroymson; Mark J. Peterson; R. Trent Jett; Natalie A. Griffiths; Evin T. Carter; Allison M. Fortner; Christopher R. DeRolph; Peijia Ku; Paul G. Matson; Rachel M. Pilla; Teresa J. Mathews (Journal of Hazardous Materials, 2024)

Positive association of SARS-CoV-2 RNA concentrations in wastewater and reported COVID-19 cases in Singapore – A study across three populations - Yvonne Hui Min Wong; Jue Tao Lim; Jane Griffiths; Benjamin Lee; Dzulkhairul Maliki; Janelle Thompson; Michelle Wong; Sae-Rom Chae; Yee Leong Teoh; Zheng Jie Marc Ho; Vernon Lee; Alex R. Cook; et al. (Science of The Total Environment, 2023)

The power of eDNA sampling to investigate the impact of Australian mega-fires on platypus occupancy - Emily F. McColl-Gausden; Josh Griffiths; Luke Collins; Andrew R. Weeks; Reid Tingley (Biological Conservation, 2023)

Exonic mutations in cell–cell adhesion may contribute to CADASIL-related CSVD pathology - Paul J. Dunn; Rodney A. Lea; Neven Maksemous; Robert A. Smith; Heidi G. Sutherland; Larisa M. Haupt; Lyn R. Griffiths (Human Genetics, 2023)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a condition caused by mutations in NOTCH3 and results in a phenotype characterised by recurrent strokes, vascular dementia and migraines. Whilst a genetic basis for the disease is known, the molecular mechanisms underpinning the pathology of CADASIL are still yet to be determined. Studies conducted at the Genomics Research Centre (GRC) have also identified that only 15–23% of individuals clinically suspected of CADASIL have mutations in NOTCH3. Based on this, whole exome sequencing was used to identify novel genetic variants for CADASIL-like cerebral small-vessel disease (CSVD). Analysis of functionally important variants in 50 individuals was investigated using overrepresentation tests in Gene ontology software to identify biological processes that are potentially affected in this group of patients. Further investigation of the genes in these processes was completed using the TRAPD software to identify if there is an increased number (burden) of mutations that are associated with CADASIL-like pathology. Results from this study identified that cell–cell adhesion genes were positively overrepresented in the PANTHER GO-slim database. TRAPD burden testing identified n = 15 genes that had a higher number of rare (MAF < 0.001) and predicted functionally relevant (SIFT < 0.05, PolyPhen > 0.8) mutations compared to the gnomAD v2.1.1 exome control dataset. Furthermore, these results identified ARVCF , GPR17 , PTPRS , and CELSR1 as novel candidate genes in CADASIL-related pathology. This study identified a novel process that may be playing a role in the vascular damage related to CADASIL-related CSVD and implicated n = 15 genes in playing a role in the disease.

A holistic and comprehensive data approach validates the distribution of the critically endangered flapper skate ( Dipturus intermedius ) - Amy Garbett; Sophie L. Loca; Thomas Barreau; Manuel Biscoito; Caroline Bradley; Joe Breen; Maurice Clarke; Jim R. Ellis; Andrew M. Griffiths; Gary Hannon; Klara Jakobsdóttir; Claudia Junge; et al. (Journal of Fish Biology, 2023)
Morphological similarities between skates of the genus Dipturus in the north‐eastern Atlantic and Mediterranean have resulted in longstanding confusion, misidentification and misreporting. Current evidence indicates that the common skate is best explained as two species, the flapper skate ( Dipturus intermedius ) and the common blue skate ( D. batis ). However, some management and conservation initiatives developed prior to the separation continue to refer to common skate (as ‘ D. batis’ ). This taxonomic uncertainty can lead to errors in estimating population viability, distribution range, and impact on fisheries management and conservation status. Here, we demonstrate how a concerted taxonomic approach, using molecular data and a combination of survey, angler and fisheries data, in addition to expert witness statements, can be used to build a higher resolution picture of the current distribution of D. intermedius . Collated data indicate that flapper skate has a more constrained distribution compared to the perceived distribution of the ‘common skate’, with most observations recorded from Norway and the western and northern seaboards of Ireland and Scotland, with occasional specimens from Portugal and the Azores. Overall, the revised spatial distribution of D. intermedius has significantly reduced the extant range of the species, indicating a possibly fragmented distribution range.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Sparing old-growth maximises conservation outcomes within selectively logged Amazonian rainforest - Gianluca Cerullo; Filipe França; Tom Finch; Philip Erm; Hannah Griffiths; Julio Louzada; Chris G. Bousfield; Mike R. Massam; Carlos A. Peres; Jos Barlow; Rhys E. Green; David P. Edwards; et al. (Biological Conservation, 2023)

Whole Exome Sequencing of Hemiplegic Migraine Patients Shows an Increased Burden of Missense Variants in CACNA1H and CACNA1I Genes - Neven Maksemous; Aster V. E. Harder; Omar Ibrahim; Lisanne S. Vijfhuizen; Heidi Sutherland; Nadine Pelzer; Irene de Boer; Gisela M. Terwindt; Rodney A. Lea; Arn M. J. M. van den Maagdenberg; Lyn R. Griffiths (Molecular Neurobiology, 2023)
Hemiplegic migraine (HM) is a rare subtype of migraine with aura. Given that causal missense mutations in the voltage-gated calcium channel α1A subunit gene CACNA1A have been identified in a subset of HM patients, we investigated whether HM patients without a mutation have an increased burden of such variants in the “ CACNA1x gene family”. Whole exome sequencing data of an Australian cohort of unrelated HM patients ( n = 184), along with public data from gnomAD, as controls, was used to assess the burden of missense variants in CACNA1x genes. We performed both a variant and a subject burden test. We found a significant burden for the number of variants in CACNA1E ( p = 1.3 × 10 −4 ), CACNA1H ( p < 2.2 × 10 −16 ) and CACNA1I ( p < 2.2 × 10 −16 ). There was also a significant burden of subjects with missense variants in CACNA1E ( p = 6.2 × 10 −3 ), CACNA1H ( p < 2.2 × 10 −16 ) and CACNA1I ( p < 2.2 × 10 −16 ). Both the number of variants and number of subjects were replicated for CACNA1H ( p = 3.5 × 10 −8 ; p = 0.012) and CACNA1I ( p = 0.019, p = 0.044), respectively, in a Dutch clinical HM cohort ( n = 32), albeit that CACNA1I did not remain significant after multiple testing correction. Our data suggest that HM, in the absence of a single causal mutation, is a complex trait, in which an increased burden of missense variants in CACNA1H and CACNA1I may contribute to the risk of disease.

Differential Strigeid Infection Patterns in Male Morphotypes of Bluegill Sunfish (Lepomis macrochirus) - Erin Atkinson; Brandi Griffith Keller; Nicholas S. Strait; Victoria L. Krist; Michael R. Zimmermann (Acta Parasitologica, 2023)

Soil bacterial and fungal communities show within field heterogeneity that varies by land management and distance metric - Fiona M. Seaton; Rob I. Griffiths; Tim Goodall; Inma Lebron; Lisa R. Norton (Soil Biology and Biochemistry, 2023)

Prevalence of Food Insecurity Among Cancer Survivors in the United States: A Scoping Review - Kim Robien; Michelle Clausen; Elaine Sullo; Yvonne R. Ford; Kathleen A. Griffith; Daisy Le; Karen E. Wickersham; Sherrie Flynt Wallington (Journal of the Academy of Nutrition and Dietetics, 2023)

Holocene forcing of East Asian hydroclimate recorded in a subtropical peatland from southeastern China - Xianyu Huang; Hongbin Zhang; Michael L. Griffiths; Bingyan Zhao; Francesco S. R. Pausata; Clay Tabor; Junwu Shu; Shucheng Xie (Climate Dynamics, 2023)

Whole-Ecosystem Warming Increases Plant-Available Nitrogen and Phosphorus in an Ombrotrophic Bog - Colleen M. Iversen; John Latimer; Deanne J. Brice; Joanne Childs; Holly M. Vander Stel; Camille E. Defrenne; Jake Graham; Natalie A. Griffiths; Avni Malhotra; Richard J. Norby; Keith C. Oleheiser; Jana R. Phillips; et al. (Ecosystems, 2023)

Patient–Specific Immersed Finite Element–Difference Model of Transcatheter Aortic Valve Replacement - Jordan A. Brown; Jae H. Lee; Margaret Anne Smith; David R. Wells; Aaron Barrett; Charles Puelz; John P. Vavalle; Boyce E. Griffith (Annals of Biomedical Engineering, 2023)
Transcatheter aortic valve replacement (TAVR) first received FDA approval for high-risk surgical patients in 2011 and has been approved for low-risk surgical patients since 2019. It is now the most common type of aortic valve replacement, and its use continues to accelerate. Computer modeling and simulation (CM&S) is a tool to aid in TAVR device design, regulatory approval, and indication in patient-specific care. This study introduces a computational fluid-structure interaction (FSI) model of TAVR with Medtronic’s CoreValve Evolut R device using the immersed finite element-difference (IFED) method. We perform dynamic simulations of crimping and deployment of the Evolut R, as well as device behavior across the cardiac cycle in a patient-specific aortic root anatomy reconstructed from computed tomography (CT) image data. These IFED simulations, which incorporate biomechanics models fit to experimental tensile test data, automatically capture the contact within the device and between the self-expanding stent and native anatomy. Further, we apply realistic driving and loading conditions based on clinical measurements of human ventricular and aortic pressures and flow rates to demonstrate that our Evolut R model supports a physiological diastolic pressure load and provides informative clinical performance predictions.

Investigating a Genetic Link Between Alzheimer’s Disease and CADASIL-Related Cerebral Small Vessel Disease - Paul J. Dunn; Rodney A. Lea; Neven Maksemous; Robert A. Smith; Heidi G. Sutherland; Larisa M. Haupt; Lyn R. Griffiths (Molecular Neurobiology, 2022)
Monogenic forms of Alzheimer’s disease (AD) have been identified through mutations in genes such as APP, PSEN1, and PSEN2 , whilst other genetic markers such as the APOE ε carrier allele status have been shown to increase the likelihood of having the disease. Mutations in these genes are not limited to AD, as APP mutations can also cause an amyloid form of cerebral small vessel disease (CSVD) known as cerebral amyloid angiopathy, whilst PSEN1 and PSEN2 are involved in NOTCH3 signalling, a process known to be dysregulated in the monogenic CSVD, cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL). The overlap between AD genes and causes of CSVD led to the hypothesis that mutations in other genes within the PANTHER AD–presenilin pathway may be novel causes of CSVD in a cohort of clinically suspicious CADASIL patients without a pathogenic NOTCH3 mutation. To investigate this, whole exome sequencing was performed on 50 suspected CADASIL patients with no NOTCH3 mutations, and a targeted gene analysis was completed on the PANTHER. ERN1 was identified as a novel candidate CSVD gene following predicted pathogenic gene mutation analysis. Rare variant burden testing failed to identify an association with any gene; however, it did show a nominally significant link with ERN1 and TRPC3. This study provides evidence to support a genetic overlap between CSVD and Alzheimer’s disease.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Food falls in the deep northwestern Weddell Sea - Julian B. Stauffer; Autun Purser; Huw J. Griffiths; Craig R. Smith; Henk-Jan T. Hoving (Frontiers in Marine Science, 2022)
When pelagic organisms die and fall onto the deep-sea floor they create food falls, i.e., parcels of organic enrichment that subsidize deep benthic scavenging communities. The diversity and quantities of food falls remain unstudied for many ocean regions since they are stochastically deposited and rapidly scavenged. The Southern Ocean habitat supports large populations of megafauna but few food falls have been documented. To investigate the diversity and quantity of food falls in the northwestern Weddell Sea, we analyzed 8476 images from the deep seafloor that were captured during the expedition PS118 on RV Polarstern in 2019 by the camera system OFOBS (Ocean Floor Observation and Bathymetry System). OFOBS was towed 1.5 m above the seafloor along five transects (400 to 2200 m seafloor depth) east of the Antarctic Peninsula. We observed the carcasses of one baleen whale, one penguin, and four fish at depths of 647 m, 613 m, 647 m, 2136 m, 2165 m, and 2112 m, respectively, as well as associated scavenging fauna. To the best of our knowledge, we describe here the first in situ observations of deep-sea food falls for penguins and fish in the Southern Ocean. While the whale carcass seemed in an intermediate successional stage, both the penguin and the fish were likely recently deposited and three of the fish potentially resulted from fishery discards. Our relatively small data set suggests that a diverse array of food falls provide nutrients to the slopes of the Powell Basin.

Managing non-target wildlife mortality whilst using rodenticides to eradicate invasive rodents on islands - Paula A. Castaño; Karl J. Campbell; Greg S. Baxter; Victor Carrión; Francesca Cunninghame; Penny Fisher; Richard Griffiths; Chad C. Hanson; Gregg R. Howald; Wesley J. Jolley; Bradford S. Keitt; Pete J. McClelland; et al. (Biological Invasions, 2022)

Investigation of Mitochondrial Related Variants in a Cerebral Small Vessel Disease Cohort - P. J. Dunn; N. R. Harvey; N. Maksemous; R. A. Smith; H. G. Sutherland; L. M. Haupt; L. R. Griffiths (Molecular Neurobiology, 2022)
Monogenic forms of cerebral small vessel disease (CSVD) can be caused by both variants in nuclear DNA and mitochondrial DNA (mtDNA). Mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) is known to have a phenotype similar to Cerebral Autosomal Dominant Arteriopathy with Sub-cortical Infarcts and Leukoencephalopathy (CADASIL), and can be caused by variants in the mitochondrial genome and in several nuclear-encoded mitochondrial protein (NEMP) genes. The aim of this study was to screen for variants in the mitochondrial genome and NEMP genes in a NOTCH3 -negative CADASIL cohort, to identify a potential link between mitochondrial dysfunction and CSVD pathology. Whole exome sequencing was performed for 50 patients with CADASIL-like symptomology on the Ion Torrent system. Mitochondrial sequencing was performed using an in-house designed protocol with sequencing run on the Ion GeneStudio S5 Plus (S5 +). NEMP genes and mitochondrial sequencing data were examined for rare (MAF < 0.001), non-synonymous variants that were predicted to have a deleterious effect on the protein. We identified 29 candidate NEMP variants that had links to either MELAS-, encephalopathy-, or Alzheimer’s disease–related phenotypes. Based on these changes, variants affecting POLG , MTO1 , LONP1 , NDUFAF6 , NDUFB3 , and TCIRG1 were thought to play a potential role in CSVD pathology in this cohort. Overall, the exploration of the mitochondrial genome identified a potential role for mitochondrial related proteins and mtDNA variants contributing to CSVD pathologies.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Proteomic changes associated with predator‐induced morphological defences in oysters - Tyler G. Evans; Jillian M. Bible; Ashley Maynard; Kaylee R. Griffith; Eric Sanford; Dietmar Kültz (Molecular Ecology, 2022)
Inducible prey defences occur when organisms undergo plastic changes in phenotype to reduce predation risk. When predation pressure varies persistently over space or time, such as when predator and prey co‐occur over only part of their biogeographic ranges, prey populations can become locally adapted in their inducible defences. In California estuaries, native Olympia oyster ( Ostrea lurida ) populations have evolved disparate phenotypic responses to an invasive predator, the Atlantic oyster drill ( Urosalpinx cinerea ). In this study, oysters from an estuary with drills, and oysters from an estuary without drills, were reared for two generations in a laboratory common garden, and subsequently exposed to cues from Atlantic drills. Comparative proteomics was then used to investigate molecular mechanisms underlying conserved and divergent aspects of their inducible defences. Both populations developed smaller, thicker, and harder shells after drill exposure, and these changes in shell phenotype were associated with upregulation of calcium transport proteins that could influence biomineralization. Inducible defences evolve in part because defended phenotypes incur fitness costs when predation risk is low. Immune proteins were downregulated by both oyster populations after exposure to drills, implying a trade‐off between biomineralization and immune function. Following drill exposure, oysters from the population that co‐occurs with drills grew smaller shells than oysters inhabiting the estuary not yet invaded by the predator. Variation in the response to drills between populations was associated with isoform‐specific protein expression. This trend suggests that a stronger inducible defence response evolved in oysters that co‐occur with drills through modification of an existing mechanism.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Discriminating head trauma outcomes using machine learning and genomics - Omar Ibrahim; Heidi G. Sutherland; Rodney A. Lea; Fatima Nasrallah; Neven Maksemous; Robert A. Smith; Larisa M. Haupt; Lyn R. Griffiths (Journal of Molecular Medicine, 2022)

Maternal Nanomaterial Inhalation Exposure: Critical Gestational Period in the Uterine Microcirculation is Angiotensin II Dependent - Krista L. Garner; Elizabeth C. Bowdridge; Julie A. Griffith; Evan DeVallance; Madison G. Seman; Kevin J. Engels; Caroline P. Groth; William T. Goldsmith; Kim Wix; Thomas P. Batchelor; Timothy R. Nurkiewicz (Cardiovascular Toxicology, 2022)

Understanding and managing the interactive impacts of growth in urban land use and climate change on freshwater biota: A case study using the platypus ( Ornithorhynchus anatinus ) - Rhys A. Coleman; Yung En Chee; Nick R. Bond; Andrew Weeks; Josh Griffiths; Melody Serena; Geoff A. Williams; Christopher J. Walsh (Global Change Biology, 2022)
Globally, urban expansion and climate change interact to threaten stream ecosystems and are accelerating the loss of aquatic biodiversity. Waterway managers urgently need tools to understand the potential combined impacts of urbanization and climate change and to identify effective mitigating management interventions for protecting freshwater biota. We address this challenge using the semi‐aquatic mammal the platypus ( Ornithorhynchus anatinus ) as a focal species. We developed high‐resolution environmental spatial data for stream networks and spatially explicit habitat suitability models (HSMs) to explore the impact of threats and to identify the combination of management actions most likely to maintain or improve habitat suitability over the next 50 years in greater Melbourne, Australia. We developed and evaluated platypus HSMs (males‐and‐females and females‐only) including validation using an independent environmental DNA data set. Platypus occurred more commonly in larger, cooler streams with greater catchment‐weighted discharge, following periods of greater stream flow. They were positively associated with near‐stream forest cover and negatively associated with annual air temperature and urban stormwater runoff. Extensive reductions in suitable platypus habitat are predicted to occur under urbanization and climate change scenarios, with the greatest threat expected from reduced streamflows. This emphasizes the importance of maintaining flow regimes as part of conserving platypus in the region; however, substantial additional benefit is predicted by concurrent riparian revegetation and urban stormwater management efforts (that also have the potential to contribute to the streamflow objectives). Provision of adequate streamflows in a future with increasing water demands and water security requirements will likely require creative integrated water management solutions. Our high‐resolution stream network and HSMs have allowed predictions of potential range‐shifts due to urban expansion and climate change impacts at management‐relevant scales and at the whole‐of‐landscape scale. This has enabled systematic strategic planning, priority action planning and target setting in strategic policy development.

Poor relationships between NEON Airborne Observation Platform data and field‐based vegetation traits at a mesic grassland - Stephanie Pau; Jesse B. Nippert; Ryan Slapikas; Daniel Griffith; Seton Bachle; Brent R. Helliker; Rory C. O’Connor; William J. Riley; Christopher J. Still; Marissa Zaricor (Ecology, 2022)
Understanding spatial and temporal variation in plant traits is needed to accurately predict how communities and ecosystems will respond to global change. The National Ecological Observatory Network’s (NEON’s) Airborne Observation Platform (AOP) provides hyperspectral images and associated data products at numerous field sites at 1 m spatial resolution, potentially allowing high‐resolution trait mapping. We tested the accuracy of readily available data products of NEON’s AOP, such as Leaf Area Index (LAI), Total Biomass, Ecosystem Structure (Canopy height model [CHM]), and Canopy Nitrogen, by comparing them to spatially extensive field measurements from a mesic tallgrass prairie. Correlations with AOP data products exhibited generally weak or no relationships with corresponding field measurements. The strongest relationships were between AOP LAI and ground‐measured LAI ( r = 0.32) and AOP Total Biomass and ground‐measured biomass ( r = 0.23). We also examined how well the full reflectance spectra (380–2,500 nm), as opposed to derived products, could predict vegetation traits using partial least‐squares regression (PLSR) models. Among all the eight traits examined, only Nitrogen had a validation of more than 0.25. For all vegetation traits, validation ranged from 0.08 to 0.29 and the range of the root mean square error of prediction (RMSEP) was 14–64%. Our results suggest that currently available AOP‐derived data products should not be used without extensive ground‐based validation. Relationships using the full reflectance spectra may be more promising, although careful consideration of field and AOP data mismatches in space and/or time, biases in field‐based measurements or AOP algorithms, and model uncertainty are needed. Finally, grassland sites may be especially challenging for airborne spectroscopy because of their high species diversity within a small area, mixed functional types of plant communities, and heterogeneous mosaics of disturbance and resource availability. Remote sensing observations are one of the most promising approaches to understanding ecological patterns across space and time. But the opportunity to engage a diverse community of NEON data users will depend on establishing rigorous links with in‐situ field measurements across a diversity of sites.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Novel compound heterozygous missense mutations in GDAP1 cause Charcot–Marie–Tooth type 4A - HUIQIN XUE; NEVEN MAKSEMOUS; DAVID SIDHOM; LAN MA; SHAOHUI CHEN; JIANRUI WU; YU FENG; LARISA M. HAUPT; LYN R. GRIFFITHS (Journal of Genetics, 2021)

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Resolving the spatial distributions of Dipturus intermedius and Dipturus batis—the two taxa formerly known as the ‘common skate’ - Maisie Bache-Jeffreys; Bárbara Lins Caldas de Moraes; Rachel E. Ball; Gui Menezes; Jónbjörn Pálsson; Christophe Pampoulie; Jamie R. Stevens; Andrew M. Griffiths (Environmental Biology of Fishes, 2021)
Batoid fishes are among the most endangered marine vertebrates, yet conservation efforts have been confounded by incomplete taxonomy. Evidence suggest that the critically endangered ‘common skate’ actually represents two species: the flapper skate ( Dipturus intermedius ) and the blue skate ( Dipturus batis ). However, knowledge of the geographic range of these two nominal species is limited. Here, DNA sequencing is used to distinguish these species, allowing their spatial distributions to be clarified. These records were also used as the basis for species distribution modelling, providing the first broad scale models for each species across the Northeast Atlantic. Samples were obtained from Iceland, the UK (specifically Shetland), the North Sea and the Azores. Results suggest that D. batis was commonly distributed in the Western Approaches and Celtic Sea, extending out to Rockall and Iceland. D. intermedius generally appears to be less abundant, but was most frequent around northern Scotland and Ireland, including the northern North Sea, and was also present in Portugal. Two individuals were also identified from seamounts in remote areas of the Atlantic around the Azores, the furthest south and west the species has been found. This supports reports that the flapper skate historically had a much wider distribution (which was also highlighted in the distribution model), emphasising the large scale over which fisheries may have led to extirpations. Furthermore, these Azorean samples shared a unique control region haplotype, highlighting the importance of seamounts in preserving genetic diversity.

South African marine citizen science – benefits, challenges and future directions - WM Potts; JB Mann-Lang; BQ Mann; CL Griffiths; CG Attwood; AD de Blocq; SH Elwen; R Nel; KJ Sink; R Thornycroft (African Journal of Marine Science, 2021)

Yellowfin Tuna Behavioural Ecology and Catchability in the South Atlantic: The Right Place at the Right Time (and Depth) - Serena R. Wright; David Righton; Joachim Naulaerts; Robert J. Schallert; Chris A. Griffiths; Taylor Chapple; Daniel Madigan; Vladimir Laptikhovsky; Victoria Bendall; Rhys Hobbs; Doug Beare; Elizabeth Clingham; et al. (Frontiers in Marine Science, 2021)
The yellowfin tuna ( Thunnus albacares: YFT) is a widely distributed, migratory species that supports valuable commercial fisheries. Landings of YFT are seasonally and spatially variable, reflecting changes in their availability and accessibility to different fleets and metiers which, in turn, has implications for sustainable management. Understanding the dynamics of YFT behaviour and how it is affected by biological and ecological factors is therefore of consequence to fisheries management design. Archival and pop-up satellite tags (PSAT) were used in the South Atlantic Ocean around St Helena between 2015 and 2020 to collect information on the movements, foraging and locomotory behaviour of YFT. The study aimed to (1) identify vertical behaviour of YFT within St Helena’s EEZ; (2) assess the timing and depth of potential feeding events and (3) to use the information to inform on the catchability of YFT to the local pole and line fishing fleet. Results indicate that the YFT daytime behaviour shifted between shallow with high incidence of fast starts in surface waters in summer months (December to April), to deep with high incidence of strikes at depth in colder months (May to November). Catchability of YFT was significantly reduced between May and November as YFT spent more time at depths below 100 m during the day, which coincides with a reduction in the quantity of YFT caught by the inshore fleet.

Mini review: genome and transcriptome editing using CRISPR-cas systems for haematological malignancy gene therapy - Esther K. Elliott; Larisa M. Haupt; Lyn R. Griffiths (Transgenic Research, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A Hybrid Model-Based Adaptive Framework for the Analysis of Climate Change Impact on Reservoir Performance - P. Biglarbeigi; W. A. Strong; D. Finlay; R. McDermott; P. Griffiths (Water Resources Management, 2020)
Climate change and population growth have influenced social and physical water scarcity in many regions. Accordingly, the future performance of water storage reservoirs, as one of the fundamental elements in the water resource management, are anticipated to be affected by climate change. This study reports on a framework that can model Reliability-Resiliency-Vulnerability (RRV) measures of water reservoirs in the context of climate change. The framework first develops a hydrological model of a reservoir system using its historical data. The model is then optimised to minimise the water deficit and flooding around the catchment area of the reservoir. The resulting optimal policies are simulated back to the model considering the GCMs. Finally, RRV indices are calculated. RRV indices are effective measures for defining the performance of reservoir systems. Reliability is defined as the probability of the failure of the system, Resiliency is defined as the time needed for the system to go back to its satisfactory state once it entered the failure state, and Vulnerability is defined as the “magnitude of the failure” of a system. The proposed framework has been applied to a reservoir system located in the south-west of Iran on the Dez river. The results show climate change may increase the reliability and resiliency of the system under study while increasing its vulnerability. Therefore, the output of this framework can also provide supplementary information to authorities and decision-makers to inform future water management and planning policies.

Subjective features of the psilocybin experience that may account for its self-administration by humans: a double-blind comparison of psilocybin and dextromethorphan - Theresa M. Carbonaro; Matthew W. Johnson; Roland R. Griffiths (Psychopharmacology, 2020)

Downregulation of Salmonella Virulence Gene Expression During Invasion of Epithelial Cells Treated with Lactococcus lactis subsp. cremoris JFR1 Requires OppA - J. S. Zhang; M. Corredig; R. Morales-Rayas; A. Hassan; M. W. Griffiths; Gisèle LaPointe (Probiotics and Antimicrobial Proteins, 2020)

A comparison between water uptake and root length density in winter wheat: effects of root density and rhizosphere properties - X. X. Zhang; P. A. Whalley; R. W. Ashton; J. Evans; M. J. Hawkesford; S. Griffiths; Z. D. Huang; H. Zhou; S. J. Mooney; W. R. Whalley (Plant and Soil, 2020)
Background and aims We aim to quantify the variation in root distribution in a set of 35 experimental wheat lines. We also compared the effect of variation in hydraulic properties of the rhizosphere on water uptake by roots. Methods We measured the root length density and soil drying in 35 wheat lines in a field experiment. A 3D numerical model was used to predict soil drying profiles with the different root length distributions and compared with measured soil drying. The model was used to test different scenarios of the hydraulic properties of the rhizosphere. Results We showed that wheat lines with no detectable differences in root length density can induce soil drying profiles with statistically significant differences. Our data confirmed that a root length density of at least 1 cm/cm 3 is needed to drain all the available water in soil. In surface layers where the root length density was far greater than 1 cm/cm 3 water uptake was independent of rooting density due to competition for water. However, in deeper layers where root length density was less than 1 cm/cm 3 , water uptake by roots was proportional to root density. Conclusion In a set of wheat lines with no detectable differences in the root length density we found significant differences in water uptake. This may be because small differences in root density at depth can result in larger differences in water uptake or that the hydraulic properties of the rhizosphere can greatly affect water uptake.

Tiered analysis of whole-exome sequencing for epilepsy diagnosis - Paul J. Dunn; Bridget H. Maher; Cassie L. Albury; Shani Stuart; Heidi G. Sutherland; Neven Maksemous; Miles C. Benton; Robert A. Smith; Larisa M. Haupt; Lyn R. Griffiths (Molecular Genetics and Genomics, 2020)

Genetic variants associated with exercise performance in both moderately trained and highly trained individuals - N. R. Harvey; S. Voisin; P. J. Dunn; H. Sutherland; X. Yan; M. Jacques; I. D. Papadimitriou; L. J. Haseler; K. J. Ashton; L. M. Haupt; N. Eynon; L. R. Griffiths (Molecular Genetics and Genomics, 2020)

Winter Rye Cover Crop Impacts on Runoff Water Quality in a Northern New York (USA) Tile-Drained Maize Agroecosystem - Keegan E. Griffith; Eric O. Young; Laura B. Klaiber; Stephen R. Kramer (Water, Air, & Soil Pollution, 2020)

Triassic to Neogene tectono-magmatic events within Lorne Basin evolution, coastal New South Wales, eastern Australia - F. L. Sutherland; I. T. Graham; H. Zwingmann; D. J. Och; C. J. Gardner; R. E. Pogson; R. J. Griffiths; A. Lay (Australian Journal of Earth Sciences, 2020)

Maternal versus artificial rearing shapes the rumen microbiome having minor long‐term physiological implications - Alejandro Belanche; David R. Yáñez‐Ruiz; Andrew P. Detheridge; Gareth W. Griffith; Alison H. Kingston‐Smith; Charles J. Newbold (Environmental Microbiology, 2019)
Summary Increasing productivity is a key target in ruminant science which requires better understanding of the rumen microbiota. This study investigated how maternal versus artificial rearing shapes the rumen microbiota using 24 sets of triplet lambs. Lambs within each sibling set were randomly assigned to natural rearing on the ewe (NN); ewe colostrum for 24 h followed by artificial milk feeding (NA); and colostrum alternative and artificial milk feeding (AA). Maternal colostrum feeding enhanced VFA production at weaning but not thereafter. At weaning, lambs reared on milk replacer had no rumen protozoa and lower microbial diversity, whereas natural rearing accelerated the rumen microbial development and facilitated the transition to solid diet. Differences in the rumen prokaryotic communities disappear later in life when all lambs were grouped on the same pasture up to 23 weeks of age. However, NN animals retained higher fungal diversity and abundances of Piromyces , Feramyces and Diplodiniinae protozoa as well as higher feed digestibility (+4%) and animal growth (+6.5%) during the grazing period. Nevertheless, no correlations were found between rumen microbiota and productive outcomes. These findings suggest that the early life nutritional intervention determine the initial rumen microbial community, but the persistence of these effects later in life is weak.

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Northern areas as refugia for temperate species under current climate warming: Atlantic salmon ( Salmo salar L.) as a model in northern Europe - Jose L. Horreo; Andrew M. Griffiths; Gonzalo Machado‐Schiaffino; Jamie R. Stevens; Eva Garcia‐Vazquez (Journal of Fish Biology, 2019)
In this work, patterns of geographical genetic diversity in Atlantic salmon Salmo salar were studied across the whole Atlantic Arc; whether these patterns (and thus genetic population structure) were affected by water temperatures was also evaluated. Salmo salar populations were characterized using microsatellite loci and then analysed with reference to ocean surface temperature data from across the region. Analysis showed the presence of a latitudinal cline of genetic variability (higher in northern areas) and water temperatures (sea surface temperatures) determining genetic population structure (the latter in combination with genetic drift in southern populations). Under the current global change scenario, northern areas of Europe would constitute refugia for diversity in the future. This is effectively the inverse of what appears to have happened in glacial refugia during the last glacial maximum. From this perspective, the still abundant and large northern populations S. salar should be considered as precious as the small almost relict southern ones and given appropriate protection. Careful management of the species, coordinated across countries and latitudes, is needed in order to avoid its extinction in Europe.

Correction to: Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Double-blind comparison of the two hallucinogens psilocybin and dextromethorphan: effects on cognition - Frederick S. Barrett; Theresa M. Carbonaro; Ethan Hurwitz; Matthew W. Johnson; Roland R. Griffiths (Psychopharmacology, 2018)

Temperature, Acidification, and Food Supply Interact to Negatively Affect the Growth and Survival of the Forage Fish, Menidia beryllina (Inland Silverside), and Cyprinodon variegatus (Sheepshead Minnow) - Christopher J. Gobler; Lucas R. Merlo; Brooke K. Morrell; Andrew W. Griffith (Frontiers in Marine Science, 2018)

Understanding and managing fish populations: keeping the toolbox fit for purpose - J. R. Paris; K. D. Sherman; E. Bell; C. Boulenger; C. Delord; M. B. M. El‐Mahdi; E. A. Fairfield; A. M. Griffiths; C. Gutmann Roberts; R. D. Hedger; L. E. Holman; L. H. Hooper; et al. (Journal of Fish Biology, 2018)
Wild fish populations are currently experiencing unprecedented pressures, which are projected to intensify in the coming decades. Developing a thorough understanding of the influences of both biotic and abiotic factors on fish populations is a salient issue in contemporary fish conservation and management. During the 50th Anniversary Symposium of The Fisheries Society of the British Isles at the University of Exeter, UK, in July 2017, scientists from diverse research backgrounds gathered to discuss key topics under the broad umbrella of ‘Understanding Fish Populations’. Below, the output of one such discussion group is detailed, focusing on tools used to investigate natural fish populations. Five main groups of approaches were identified: tagging and telemetry; molecular tools; survey tools; statistical and modelling tools; tissue analyses. The appraisal covered current challenges and potential solutions for each of these topics. In addition, three key themes were identified as applicable across all tool‐based applications. These included data management, public engagement, and fisheries policy and governance. The continued innovation of tools and capacity to integrate interdisciplinary approaches into the future assessment and management of fish populations is highlighted as an important focus for the next 50 years of fisheries research.

Double-blind comparison of the two hallucinogens psilocybin and dextromethorphan: similarities and differences in subjective experiences - Theresa M. Carbonaro; Matthew W. Johnson; Ethan Hurwitz; Roland R. Griffiths (Psychopharmacology, 2018)

Liposomal Irinotecan Accumulates in Metastatic Lesions, Crosses the Blood-Tumor Barrier (BTB), and Prolongs Survival in an Experimental Model of Brain Metastases of Triple Negative Breast Cancer - Afroz S. Mohammad; Jessica I. Griffith; Chris E. Adkins; Neal Shah; Emily Sechrest; Emma L. Dolan; Tori B. Terrell-Hall; Bart S. Hendriks; Helen Lee; Paul R. Lockman (Pharmaceutical Research, 2018)

Lipid (per) oxidation in mitochondria: an emerging target in the ageing process? - O. S. Ademowo; H. K. I. Dias; D. G. A. Burton; H. R. Griffiths (Biogerontology, 2017)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Will the same ex situ protocols give similar results for closely related species? - M. Patrick Griffith; Michael Calonje; Alan W. Meerow; Javier Francisco-Ortega; Lindy Knowles; Rudy Aguilar; Freddy Tut; Vanessa Sánchez; Abby Meyer; Larry R. Noblick; Tracy M. Magellan (Biodiversity and Conservation, 2017)

Mutualistic interaction between dichloromethane‐ and chloromethane‐degrading bacteria in an anaerobic mixed culture - Gao Chen; Sara Kleindienst; Daniel R. Griffiths; E. Erin Mack; Edward S. Seger; Frank E. Löffler (Environmental Microbiology, 2017)
Summary The microbial mixed culture RM grows with dichloromethane (DCM) as the sole energy source generating acetate, methane, chloride and biomass as products. Chloromethane (CM) was not an intermediate during DCM utilization consistent with the observation that CM could not replace DCM as a growth substrate. Interestingly, cultures that received DCM and CM together degraded both compounds concomitantly. Transient hydrogen (H 2 ) formation reaching a maximum concentration of 205 ± 13 ppmv was observed in cultures growing with DCM, and the addition of exogenous H 2 at concentrations exceeding 3000 ppmv impeded DCM degradation. In contrast, CM degradation in culture RM had a strict requirement for H 2 . Following five consecutive transfers on CM and H 2 , Acetobacterium 16S rRNA gene sequences dominated the culture and the DCM‐degrader Candidatus Dichloromethanomonas elyunquensis was eliminated, consistent with the observation that the culture lost the ability to degrade DCM. These findings demonstrate that culture RM harbours different populations responsible for anaerobic DCM and CM metabolism, and further imply that the DCM and CM degradation pathways are mechanistically distinct. H 2 generated during DCM degradation is consumed by the hydrogenotrophic CM degrader, or may fuel other hydrogenotrophic processes, including organohalide respiration, methanogenesis and H 2 /CO 2 reductive acetogenesis.

Mollusc species richness and abundance from shelf to abyssal depths in the Ross Sea (Antarctica): the importance of fine-mesh-towed gears and implications for future sampling - Claudio Ghiglione; Maria Chiara Alvaro; Paola Piazza; David Bowden; Huw J. Griffiths; Cinzia Carota; Consuelo R. Nava; Stefano Schiaparelli (Polar Biology, 2017)

Ion channelopathies and migraine pathogenesis - Cassie L. Albury; Shani Stuart; Larisa M. Haupt; Lyn R. Griffiths (Molecular Genetics and Genomics, 2017)

Global synthesis of the temperature sensitivity of leaf litter breakdown in streams and rivers - Jennifer J. Follstad Shah; John S. Kominoski; Marcelo Ardón; Walter K. Dodds; Mark O. Gessner; Natalie A. Griffiths; Charles P. Hawkins; Sherri L. Johnson; Antoine Lecerf; Carri J. LeRoy; David W. P. Manning; Amy D. Rosemond; et al. (Global Change Biology, 2017)
Streams and rivers are important conduits of terrestrially derived carbon (C) to atmospheric and marine reservoirs. Leaf litter breakdown rates are expected to increase as water temperatures rise in response to climate change. The magnitude of increase in breakdown rates is uncertain, given differences in litter quality and microbial and detritivore community responses to temperature, factors that can influence the apparent temperature sensitivity of breakdown and the relative proportion of C lost to the atmosphere vs. stored or transported downstream. Here, we synthesized 1025 records of litter breakdown in streams and rivers to quantify its temperature sensitivity, as measured by the activation energy ( E a , in eV ). Temperature sensitivity of litter breakdown varied among twelve plant genera for which E a could be calculated. Higher values of E a were correlated with lower‐quality litter, but these correlations were influenced by a single, N‐fixing genus ( Alnus ). E a values converged when genera were classified into three breakdown rate categories, potentially due to continual water availability in streams and rivers modulating the influence of leaf chemistry on breakdown. Across all data representing 85 plant genera, the E a was 0.34 ± 0.04 eV , or approximately half the value (0.65 eV ) predicted by metabolic theory. Our results indicate that average breakdown rates may increase by 5–21% with a 1–4 °C rise in water temperature, rather than a 10–45% increase expected, according to metabolic theory. Differential warming of tropical and temperate biomes could result in a similar proportional increase in breakdown rates, despite variation in E a values for these regions (0.75 ± 0.13 eV and 0.27 ± 0.05 eV, respectively). The relative proportions of gaseous C loss and organic matter transport downstream should not change with rising temperature given that E a values for breakdown mediated by microbes alone and microbes plus detritivores were similar at the global scale.

The importance of benthic–pelagic coupling for marine ecosystem functioning in a changing world - Jennifer R. Griffiths; Martina Kadin; Francisco J. A. Nascimento; Tobias Tamelander; Anna Törnroos; Stefano Bonaglia; Erik Bonsdorff; Volker Brüchert; Anna Gårdmark; Marie Järnström; Jonne Kotta; Martin Lindegren; et al. (Global Change Biology, 2017)
Benthic–pelagic coupling is manifested as the exchange of energy, mass, or nutrients between benthic and pelagic habitats. It plays a prominent role in aquatic ecosystems, and it is crucial to functions from nutrient cycling to energy transfer in food webs. Coastal and estuarine ecosystem structure and function are strongly affected by anthropogenic pressures; however, there are large gaps in our understanding of the responses of inorganic nutrient and organic matter fluxes between benthic habitats and the water column. We illustrate the varied nature of physical and biological benthic–pelagic coupling processes and their potential sensitivity to three anthropogenic pressures – climate change, nutrient loading, and fishing – using the Baltic Sea as a case study and summarize current knowledge on the exchange of inorganic nutrients and organic material between habitats. Traditionally measured benthic–pelagic coupling processes (e.g., nutrient exchange and sedimentation of organic material) are to some extent quantifiable, but the magnitude and variability of biological processes are rarely assessed, preventing quantitative comparisons. Changing oxygen conditions will continue to have widespread effects on the processes that govern inorganic and organic matter exchange among habitats while climate change and nutrient load reductions may have large effects on organic matter sedimentation. Many biological processes (predation, bioturbation) are expected to be sensitive to anthropogenic drivers, but the outcomes for ecosystem function are largely unknown. We emphasize how improved empirical and experimental understanding of benthic–pelagic coupling processes and their variability are necessary to inform models that can quantify the feedbacks among processes and ecosystem responses to a changing world.

A genome-wide association study of essential hypertension in an Australian population using a DNA pooling approach - Javed Y. Fowdar; Rebecca Grealy; Yi Lu; Lyn R. Griffiths (Molecular Genetics and Genomics, 2017)

Effects of caffeine on alcohol reinforcement: beverage choice, self-administration, and subjective ratings - Mary M. Sweeney; Steven E. Meredith; Daniel P. Evatt; Roland R. Griffiths (Psychopharmacology, 2017)

Inducible defenses in Olympia oysters in response to an invasive predator - Jillian M. Bible; Kaylee R. Griffith; Eric Sanford (Oecologia, 2017)

Diurnal Fluctuations in Acidification and Hypoxia Reduce Growth and Survival of Larval and Juvenile Bay Scallops (Argopecten irradians) and Hard Clams (Mercenaria mercenaria) - Christopher J. Gobler; Hannah R. Clark; Andrew W. Griffith; Mark W. Lusty (Frontiers in Marine Science, 2017)

Correction: Reporting costs for invasive vertebrate eradications - N. D. Holmes; K. J. Campbell; B. Keitt; R. Griffiths; J. Beek; C. J. Donlan; K. Broome (Biological Invasions, 2016)

Discordance between morphological and taxonomic diversity: land snails of oceanic archipelagos - Kostas A. Triantis; François Rigal; Christine E. Parent; Robert A. D. Cameron; Bernd Lenzner; Aristeidis Parmakelis; Norine W. Yeung; María R. Alonso; Miguel Ibáñez; António M. de Frias Martins; Dinarte N. F. Teixeira; Owen L. Griffiths; et al. (Journal of Biogeography, 2016)
Aim Morphological and taxonomic diversity are intuitive measures of biological diversity. Previous studies have shown discordance between these measures at large spatial and temporal scales, but the implications of this pattern for the underlying processes are not understood. Using oceanic archipelagos as spatial units, we examine potential links between the morphological and taxonomic diversity of their land snail faunas in a biogeographical framework. Location Eleven major oceanic archipelagos. Methods For each archipelago, we assembled lists of indigenous land snail species, classified by family and genus, with shell height and width for each species (1723 species in total). We used biogeographic and climatic variables as potential predictors of diversity patterns. We employed regression analyses to evaluate (1) whether morphological diversity scales with taxonomic diversity at the species, genus or family level, and (2) whether morphological and taxonomic diversity correlate similarly with biogeographic/climatic factors. We also assessed which taxonomic level contributes most to morphological variation within archipelagos. Results Morphological diversity across archipelagos was strongly related to genus but not species richness. Within archipelagos, morphological variation reflected differences among genera and families but not species. Species richness was best explained by archipelago area, but morphological diversity was not significantly related to any of the physical features of archipelagos. Main conclusions Across archipelagos, species richness and morphological diversity of land snail faunas are decoupled. The relationship between species richness and the available ecological space (captured mainly by area) indicates the prevalence of niche‐based processes while, for morphological diversity, the strong conservatism of morphology at the genus level suggests the presence of diversification‐based limits. Assuming genera effectively reflect diversification, our findings indicate that morphological space on oceanic archipelagos depends primarily on the number of evolutionary units that have colonized and/or diversified through time.

Determining the correct identity of South African Marthasterias (Echinodermata: Asteroidea) - AG Wright; R Pérez-Portela; CL Griffiths (African Journal of Marine Science, 2016)

Population‐level consequences for wild fish exposed to sublethal concentrations of chemicals – a critical review - Patrick B Hamilton; Ian G Cowx; Marjorie F Oleksiak; Andrew M Griffiths; Mats Grahn; Jamie R Stevens; Gary R Carvalho; Elizabeth Nicol; Charles R Tyler (Fish and Fisheries, 2016)
Concentrated chemical spills have been shown to impact adversely on fish populations and even cause localized population extinctions. Evaluating population‐level impacts of sublethal exposure concentrations is, however, complex and confounded by other environmental pressures. Applying effect measures derived from laboratory‐based chemical exposures to impacts in wild fish populations is constrained by uncertainty on how biochemical response measures (biomarkers) translate into health outcomes, lack of available data for chronic exposures and the many uncertainties in available fish population models. Furthermore, wild fish show phenotypic plasticity and local adaptations can occur that adds geographic and temporal variance on responses. Such population‐level factors are rarely considered in the chemical risk assessment process and can probably be derived only from studies on wild fish. Molecular technologies, including microsatellite and SNP genotyping, and RNAS eq for gene expression studies, are advancing our understanding of mechanisms of eco‐toxicological response, tolerance, adaptation and selection in wild populations. We examine critically the application of such approaches with examples including using microsatellites that has identified roach ( Rutilus rutilus ) populations living in rivers contaminated with sewage effluents that are self‐sustaining, and studies of stickleback ( Gasterosteus aculeatus ) and killifish ( Fundulus heteroclitus ) that have identified genomic regions under selection putatively related to pollution tolerance. Integrating data on biological effects between laboratory‐based studies and wild populations, and building understanding on adaptive responses to sublethal exposure are some of the priority research areas for more effective evaluation of population risks and resilience to contaminant exposure.

Resolving taxonomic uncertainty in vulnerable elasmobranchs: are the Madeira skate (Raja maderensis) and the thornback ray (Raja clavata) distinct species? - Rachel E. Ball; Barbara Serra-Pereira; Jim Ellis; Martin J. Genner; Samuel Iglésias; Andrew F. Johnson; Catherine S. Jones; Rob Leslie; Jennifer Lewis; Stefano Mariani; Gui Menezes; Francis Neat; et al. (Conservation Genetics, 2016)
Skates and rays constitute the most speciose group of chondrichthyan fishes, yet are characterised by remarkable levels of morphological and ecological conservatism. They can be challenging to identify, which makes monitoring species compositions for fisheries management purposes problematic. Owing to their slow growth and low fecundity, skates are vulnerable to exploitation and species exhibiting endemism or limited ranges are considered to be the most at risk. The Madeira skate Raja maderensis is endemic and classified as ‘Data Deficient’ by the IUCN, yet its taxonomic distinctiveness from the morphologically similar and more wide-ranging thornback ray Raja clavata is unresolved. This study evaluated the sequence divergence of both the variable control region and cytochrome oxidase I ‘DNA barcode’ gene of the mitochondrial genome to elucidate the genetic differentiation of specimens identified as R. maderensis and R. clavata collected across much of their geographic ranges. Genetic evidence was insufficient to support the different species designations. However regardless of putative species identification, individuals occupying waters around the Azores and North African Seamounts represent an evolutionarily significant unit worthy of special consideration for conservation management.

Innovative biomarkers for predicting type 2 diabetes mellitus: relevance to dietary management of frailty in older adults - John Ikwuobe; Srikanth Bellary; Helen R. Griffiths (Biogerontology, 2016)

Differences in soil micro‐eukaryotic communities over soil pH gradients are strongly driven by parasites and saprotrophs - A. Ö. C. Dupont; R. I. Griffiths; T. Bell; D. Bass (Environmental Microbiology, 2016)
Summary A recent large‐scale assessment of bacterial communities across a range of UK soil types showed that bacterial community structure was strongly determined by soil pH. We analysed a data set of eukaryotic 454 sequencing 18S rDNA from the surveyed samples and showed significant differences in eukaryotic assemblages according to pH class, mostly between low pH and higher pH soils. Soil eukaryote communities (per sample) differed most at the taxonomic rank approximating to order level. Taxonomies assigned with the P rotist R ibosomal R eference and the S ilva 119 databases were taxonomically inconsistent, mostly due to differing 18S annotations, although general structure and composition according to pH were coherent. A relatively small number of lineages, mostly putative parasitic protists and fungi, drive most differences between pH classes, with weaker contributions from bacterivores and autotrophs. Overall, soil parasites included a large diversity of alveolates, in particular apicomplexans. Phylogenetic analysis of alveolate lineages demonstrates a large diversity of unknown gregarines, novel perkinsids, coccidians, colpodellids and uncharacterized alveolates. Other novel and/or divergent lineages were revealed across the eukaryote tree of life. Our study provides an in‐depth taxonomic evaluation of micro‐eukaryotic diversity, and reveals novel lineages and insights into their relationships with environmental variables across soil gradients.

Characterization of passive permeability at the blood–tumor barrier in five preclinical models of brain metastases of breast cancer - Chris E. Adkins; Afroz S. Mohammad; Tori B. Terrell-Hall; Emma L. Dolan; Neal Shah; Emily Sechrest; Jessica Griffith; Paul R. Lockman (Clinical & Experimental Metastasis, 2016)

Impact of Diet Composition on Blood Glucose Regulation - Wendy R. Russell; Athanasia Baka; Inger Björck; Nathalie Delzenne; Dan Gao; Helen R. Griffiths; Ellie Hadjilucas; Kristiina Juvonen; Sampo Lahtinen; Mirian Lansink; Luc Van Loon; Hannu Mykkänen; et al. (Critical Reviews in Food Science and Nutrition, 2016)

Nicotine reinforcement in never-smokers - Angela N. Duke; Matthew W. Johnson; Chad J. Reissig; Roland R. Griffiths (Psychopharmacology, 2015)

Anaerobic digestion of Spirulina sp. and Scenedesmus sp.: a comparison and investigation of the impact of mechanical pre-treatment - A. E. Inglesby; M. J. Griffiths; S. T. L. Harrison; R. P. van Hille (Journal of Applied Phycology, 2015)

Common polygenic variation contributes to risk of migraine in the Norfolk Island population - A. J. Rodriguez-Acevedo; M. A. Ferreira; Miles C. Benton; Melanie A. Carless; Harald H. Goring; Joanne E. Curran; John Blangero; R. A. Lea; L. R. Griffiths (Human Genetics, 2015)

A small-scale transdisciplinary process to maximising the energy efficiency of food factories: insights and recommendations from the development of a novel heat integration framework - J. H. Miah; A. Griffiths; R. McNeill; I. Poonaji; R. Martin; S. Morse; A. Yang; J. Sadhukhan (Sustainability Science, 2015)

Reporting costs for invasive vertebrate eradications - N. D. Holmes; K. J. Campbell; B. S. Keitt; R. Griffiths; J. Beek; C. J. Donlan; K. G. Broome (Biological Invasions, 2015)

Recreational vessels as a vector for marine non-natives: developing biosecurity measures and managing risk through an in-water encapsulation system - R. C. Roche; J. M. Monnington; R. G. Newstead; K. Sambrook; K. Griffith; R. H. F. Holt; S. R. Jenkins (Hydrobiologia, 2015)

Ageing, adipose tissue, fatty acids and inflammation - Chathyan Pararasa; Clifford J. Bailey; Helen R. Griffiths (Biogerontology, 2015)

Emerging Trends in Heart Valve Engineering: Part I. Solutions for Future - Arash Kheradvar; Elliott M. Groves; Lakshmi P. Dasi; S. Hamed Alavi; Robert Tranquillo; K. Jane Grande-Allen; Craig A. Simmons; Boyce Griffith; Ahmad Falahatpisheh; Craig J. Goergen; Mohammad R. K. Mofrad; Frank Baaijens; et al. (Annals of Biomedical Engineering, 2015)

Emerging Trends in Heart Valve Engineering: Part II. Novel and Standard Technologies for Aortic Valve Replacement - Arash Kheradvar; Elliott M. Groves; Craig J. Goergen; S. Hamed Alavi; Robert Tranquillo; Craig A. Simmons; Lakshmi P. Dasi; K. Jane Grande-Allen; Mohammad R. K. Mofrad; Ahmad Falahatpisheh; Boyce Griffith; Frank Baaijens; et al. (Annals of Biomedical Engineering, 2015)

Emerging Trends in Heart Valve Engineering: Part III. Novel Technologies for Mitral Valve Repair and Replacement - Arash Kheradvar; Elliott M. Groves; Craig A. Simmons; Boyce Griffith; S. Hamed Alavi; Robert Tranquillo; Lakshmi P. Dasi; Ahmad Falahatpisheh; K. Jane Grande-Allen; Craig J. Goergen; Mohammad R. K. Mofrad; Frank Baaijens; et al. (Annals of Biomedical Engineering, 2015)

Maximizing the phylogenetic diversity of seed banks - Kate E. Griffiths; Sharon T. Balding; John B. Dickie; Gwilym P. Lewis; Tim R. Pearce; Richard Grenyer (Conservation Biology, 2015)
Ex situ conservation efforts such as those of zoos, botanical gardens, and seed banks will form a vital complement to in situ conservation actions over the coming decades. It is therefore necessary to pay the same attention to the biological diversity represented in ex situ conservation facilities as is often paid to protected‐area networks. Building the phylogenetic diversity of ex situ collections will strengthen our capacity to respond to biodiversity loss. Since 2000, the Millennium Seed Bank Partnership has banked seed from 14% of the world's plant species. We assessed the taxonomic, geographic, and phylogenetic diversity of the Millennium Seed Bank collection of legumes (Leguminosae). We compared the collection with all known legume genera, their known geographic range (at country and regional levels), and a genus‐level phylogeny of the legume family constructed for this study. Over half the phylogenetic diversity of legumes at the genus level was represented in the Millennium Seed Bank. However, pragmatic prioritization of species of economic importance and endangerment has led to the banking of a less‐than‐optimal phylogenetic diversity and prioritization of range‐restricted species risks an underdispersed collection. The current state of the phylogenetic diversity of legumes in the Millennium Seed Bank could be substantially improved through the strategic banking of relatively few additional taxa. Our method draws on tools that are widely applied to in situ conservation planning, and it can be used to evaluate and improve the phylogenetic diversity of ex situ collections. Maximizar la Riqueza Filogenética de los Bancos de Semillas

Inhaled vs. oral alprazolam: subjective, behavioral and cognitive effects, and modestly increased abuse potential - Chad J. Reissig; Joseph A. Harrison; Lawrence P. Carter; Roland R. Griffiths (Psychopharmacology, 2015)

Transmembrane channel-like (TMC) genes are required for auditory and vestibular mechanosensation - Yoshiyuki Kawashima; Kiyoto Kurima; Bifeng Pan; Andrew J. Griffith; Jeffrey R. Holt (Pflügers Archiv - European Journal of Physiology, 2015)

Computational epigenetic profiling of CpG islets in MTHFR - Keat Wei; Heidi Sutherland; Emily Camilleri; Larisa M. Haupt; Lyn R. Griffiths; Siew Hua Gan (Molecular Biology Reports, 2014)

Localization of submicron inclusion re-equilibration at healed fractures in host garnet - T. A. Griffiths; G. Habler; D. Rhede; R. Wirth; F. Ram; R. Abart (Contributions to Mineralogy and Petrology, 2014)

Pharmacokinetics and Efficacy of the Spleen Tyrosine Kinase Inhibitor R406 after Ocular Delivery for Retinoblastoma - Eleanor M. Pritchard; Elizabeth Stewart; Fangyi Zhu; Cori Bradley; Lyra Griffiths; Lei Yang; Praveen Kumar Suryadevara; Jiakun Zhang; Burgess B. Freeman; R. Kiplin Guy; Michael A. Dyer (Pharmaceutical Research, 2014)

Tiger shark (Galeocerdo cuvier) movement patterns and habitat use determined by satellite tagging in eastern Australian waters - Bonnie J. Holmes; Julian G. Pepperell; Shane P. Griffiths; Fabrice R. A. Jaine; Ian R. Tibbetts; Mike B. Bennett (Marine Biology, 2014)

Temporal Variation in the Importance of a Dominant Consumer to Stream Nutrient Cycling - Natalie A. Griffiths; Walter R. Hill (Ecosystems, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Efficiency of bacteriophage therapy against Cronobacter sakazakii in Galleria mellonella (greater wax moth) larvae - Reza Abbasifar; Andrew M. Kropinski; Parviz M. Sabour; James R. Chambers; Joanne MacKinnon; Thomas Malig; Mansel W. Griffiths (Archives of Virology, 2014)

Long‐term effects of stock transfers: synergistic introgression of allochthonous genomes in salmonids - J. L. Horreo; G. Machado‐Schiaffino; A. M. Griffiths; D. Bright; J. R. Stevens; E. Garcia‐Vazquez (Journal of Fish Biology, 2014)
The genus Salmo was employed as a model to study introgression of genes between species due to secondary contacts. Seven microsatellite loci, the LDH‐C1 * locus and the 5S ribosomal DNA were studied. Results showed the mutually enhanced introgression of allochthonous genomes into southern European salmonids. This phenomenon appears to go beyond a simple consequence of the altered behaviour of domestic individuals. Invasions of autochthonous genomes by allochthonous genes would be enhanced by human activities such as stock transfers, which would simultaneously promote allochthonous and allospecific (from other species) introgressions in a synergistic process in Atlantic salmon Salmo salar and brown trout Salmo trutta . As a minor result, the data do not support the value of the microsatellite locus SsaD486 as a species‐specific marker.

High levels of activity of bats at gold mining water bodies: implications for compliance with the International Cyanide Management Code - Stephen R. Griffiths; David B. Donato; Graeme Coulson; Linda F. Lumsden (Environmental Science and Pollution Research, 2014)

A rooftop revolution? A multidisciplinary analysis of state-level residential solar programs in New Jersey and Massachusetts - Alden B. Griffith; Monica R. Higgins; James Morton Turner (Journal of Environmental Studies and Sciences, 2014)

An ex‐tropical cyclone climatology for Auckland, New Zealand - Andrew M. Lorrey; Georgina Griffiths; Nicolas Fauchereau; Howard J. Diamond; Petra R. Chappell; James Renwick (International Journal of Climatology, 2014)
Auckland, New Zealand, is influenced by ex‐tropical cyclones ( ETCs ); however, there is no established climatology for these weather systems at present. In this study, we present a climatology of ETCs for Auckland and investigate whether their spatio‐temporal traits are influenced by large‐scale climate modes such as the El Niño‐Southern Oscillation ( ENSO ) and the Southern Annular Mode ( SAM ). We utilize the South Pacific Enhanced Archive for Tropical Cyclone research ( SPEArTC ) to establish a climatology that covers the high‐quality TC data period from 1970 to 2010. ETCs have entered a region within 550 km of Auckland city regardless of ENSO or SAM phase, and on average one event per year occurs. Peak ETC season for Auckland is during March, preceded by an increase in activity during February, with a wide‐range of meteorological impacts. Regional circulation patterns, including reduced blocking in the southwest Pacific and synoptic type presence, allow ETCs into the Auckland sector of the southwest Pacific while guiding them either to the east or west of the city.

Epiphytic seaweeds and invertebrates associated with South African populations of the rocky shore seagrass Thalassodendron leptocaule — a hidden wealth of biodiversity - CM Browne; R Milne; C Griffiths; JJ Bolton; RJ Anderson (African Journal of Marine Science, 2013)

Reproductive biology of wahoo, Acanthocybium solandri, off eastern Australia - Mitchell T. Zischke; Jessica H. Farley; Shane P. Griffiths; Ian R. Tibbetts (Reviews in Fish Biology and Fisheries, 2013)

Morph-dependent resource acquisition and fitness in a polymorphic bird - James Brazill-Boast; Simon C. Griffith; Sarah R. Pryke (Evolutionary Ecology, 2013)

The importance of health co-benefits in macroeconomic assessments of UK Greenhouse Gas emission reduction strategies - Henning Tarp Jensen; Marcus R. Keogh-Brown; Richard D. Smith; Zaid Chalabi; Alan D. Dangour; Mike Davies; Phil Edwards; Tara Garnett; Moshe Givoni; Ulla Griffiths; Ian Hamilton; James Jarrett; et al. (Climatic Change, 2013)
We employ a single-country dynamically-recursive Computable General Equilibrium model to make health-focussed macroeconomic assessments of three contingent UK Greenhouse Gas (GHG) mitigation strategies, designed to achieve 2030 emission targets as suggested by the UK Committee on Climate Change. In contrast to previous assessment studies, our main focus is on health co-benefits additional to those from reduced local air pollution. We employ a conservative cost-effectiveness methodology with a zero net cost threshold. Our urban transport strategy (with cleaner vehicles and increased active travel) brings important health co-benefits and is likely to be strongly cost-effective; our food and agriculture strategy (based on abatement technologies and reduction in livestock production) brings worthwhile health co-benefits, but is unlikely to eliminate net costs unless new technological measures are included; our household energy efficiency strategy is likely to breakeven only over the long term after the investment programme has ceased (beyond our 20 year time horizon). We conclude that UK policy makers will, most likely, have to adopt elements which involve initial net societal costs in order to achieve future emission targets and longer-term benefits from GHG reduction. Cost-effectiveness of GHG strategies is likely to require technological mitigation interventions and/or demand-constraining interventions with important health co-benefits and other efficiency-enhancing policies that promote internalization of externalities. Health co-benefits can play a crucial role in bringing down net costs, but our results also suggest the need for adopting holistic assessment methodologies which give proper consideration to welfare-improving health co-benefits with potentially negative economic repercussions (such as increased longevity).

Towards a unified paradigm for sequence‐based identification of fungi - Urmas Kõljalg; R. Henrik Nilsson; Kessy Abarenkov; Leho Tedersoo; Andy F. S. Taylor; Mohammad Bahram; Scott T. Bates; Thomas D. Bruns; Johan Bengtsson‐Palme; Tony M. Callaghan; Brian Douglas; Tiia Drenkhan; et al. (Molecular Ecology, 2013)
The nuclear ribosomal internal transcribed spacer ( ITS ) region is the formal fungal barcode and in most cases the marker of choice for the exploration of fungal diversity in environmental samples. Two problems are particularly acute in the pursuit of satisfactory taxonomic assignment of newly generated ITS sequences: (i) the lack of an inclusive, reliable public reference data set and (ii) the lack of means to refer to fungal species, for which no Latin name is available in a standardized stable way. Here, we report on progress in these regards through further development of the UNITE database ( http://unite.ut.ee ) for molecular identification of fungi. All fungal species represented by at least two ITS sequences in the international nucleotide sequence databases are now given a unique, stable name of the accession number type (e.g. H ymenoscyphus pseudoalbidus | GU 586904| SH 133781.05 FU ), and their taxonomic and ecological annotations were corrected as far as possible through a distributed, third‐party annotation effort. We introduce the term ‘species hypothesis’ ( SH ) for the taxa discovered in clustering on different similarity thresholds (97–99%). An automatically or manually designated sequence is chosen to represent each such SH. These reference sequences are released ( http://unite.ut.ee/repository.php ) for use by the scientific community in, for example, local sequence similarity searches and in the QIIME pipeline. The system and the data will be updated automatically as the number of public fungal ITS sequences grows. We invite everybody in the position to improve the annotation or metadata associated with their particular fungal lineages of expertise to do so through the new Web‐based sequence management system in UNITE .

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Human-mediated drivers of change — impacts on coastal ecosystems and marine biota of South Africa - A Mead; C L Griffiths; G M Branch; C D McQuaid; L K Blamey; J J Bolton; R J Anderson; F Dufois; M Rouault; P W Froneman; A K Whitfield; L R Harris; et al. (African Journal of Marine Science, 2013)

BDNF and TNF-α polymorphisms in memory - B. S. Yogeetha; L. M. Haupt; K. McKenzie; H. G. Sutherland; R. K. Okolicsyani; R. A. Lea; B. H. Maher; R. C. K. Chan; D. H. K. Shum; L. R. Griffiths (Molecular Biology Reports, 2013)

Turn costs change the value of animal search paths - R. P. Wilson; I. W. Griffiths; P. A. Legg; M. I. Friswell; O. R. Bidder; L. G. Halsey; S. A. Lambertucci; E. L. C. Shepard (Ecology Letters, 2013)
The tortuosity of the track taken by an animal searching for food profoundly affects search efficiency, which should be optimised to maximise net energy gain. Models examining this generally describe movement as a series of straight steps interspaced by turns, and implicitly assume no turn costs. We used both empirical‐ and modelling‐based approaches to show that the energetic costs for turns in both terrestrial and aerial locomotion are substantial, which calls into question the value of conventional movement models such as correlated random walk or Lévy walk for assessing optimum path types. We show how, because straight‐line travel is energetically most efficient, search strategies should favour constrained turn angles, with uninformed foragers continuing in straight lines unless the potential benefits of turning offset the cost.

Erratum to: High doses of dextromethorphan, an NMDA antagonist, produce effects similar to classic hallucinogens - Chad J. Reissig; Lawrence P. Carter; Matthew W. Johnson; Miriam Z. Mintzer; Margaret A. Klinedinst; Roland R. Griffiths (Psychopharmacology, 2013)

Dispersal patterns and population structuring among platypuses, Ornithorhynchus anatinus, throughout south-eastern Australia - E. M. Furlan; J. Griffiths; N. Gust; K. A. Handasyde; T. R. Grant; B. Gruber; A. R. Weeks (Conservation Genetics, 2013)

Sub-daily alias and draconitic errors in the IGS orbits - J. Griffiths; Jim R. Ray (GPS Solutions, 2013)

Agricultural land use alters the seasonality and magnitude of stream metabolism - Natalie A. Griffiths; Jennifer L. Tank; Todd V. Royer; Sarah S. Roley; Emma J. Rosi-Marshall; Matt R. Whiles; Jake J. Beaulieu; Laura T. Johnson (Limnology and Oceanography, 2013)
We present a comprehensive data set of gross primary production (GPP) and ecosystem respiration (ER) in open‐canopy, nutrient‐rich streams draining row‐crop agriculture in the midwestern United States. We used two approaches to characterize temporal and spatial variation in whole‐stream metabolism: continuous measurements in one agricultural stream for 1 yr, and periodic daily measurements in six agricultural streams on six dates spanning summer, autumn, and winter. Continuous measurements revealed high rates of GPP (range: 0.1 to 22.0 g O 2 m −2 d −1 ) and ER (range: −0.9 to −34.8 g O 2 m −2 d −1 ) that varied seasonally with light availability and temperature. GPP and ER were correlated during periods of high autotrophic production, suggesting that autotrophic respiration comprised a large portion of ER; however, the GPP : ER ratio exceeded 1 for only 4% of the year. While there were distinct temporal patterns in metabolism in one agricultural stream, rates of GPP and ER were similar among six streams when assessed via periodic daily measurements, and 26% of all periodic daily measurements were autotrophic with GPP : ER > 1. However, these periodic measurements were collected under baseflow conditions and may have overestimated the extent of autotrophy in agricultural streams. Overall, the open canopy and elevated nutrients of agricultural streams resulted in higher rates of GPP and ER compared with more pristine systems. Estimates of metabolism are needed from underrepresented systems to accurately quantify carbon fluxes from fluvial ecosystems.

Structural cladistic study of Cocoseae, subtribe Attaleinae (Arecaceae): Evaluating taxonomic limits in Attaleinae and the neotropical genus Syagrus - Larry R. Noblick; William J. Hahn; M. Patrick Griffith (Brittonia, 2013)

The first confirmed cases of full albinism in rajid species - R. E. Ball; C. S. Jones; A. Lynghammar; L. R. Noble; A. M. Griffiths (Journal of Fish Biology, 2013)
Three albino skate specimens (Rajidae) were captured from the North Sea and English Channel between 2008 and 2011. Using DNA barcoding ( COI gene) and morphometric analyses, species were identified as a spotted ray Raja montagui , a blonde ray Raja brachyura and a thornback ray Raja clavata . This finding represents the first record of full albinism (a lack of skin and retinal pigmentation) in rajid species.

Dose-related effects of salvinorin A in humans: dissociative, hallucinogenic, and memory effects - Katherine A. MacLean; Matthew W. Johnson; Chad J. Reissig; Thomas E. Prisinzano; Roland R. Griffiths (Psychopharmacology, 2013)

Cognitive effects of intramuscular ketamine and oral triazolam in healthy volunteers - Lawrence P. Carter; Bethea A. Kleykamp; Roland R. Griffiths; Miriam Z. Mintzer (Psychopharmacology, 2013)

Effects of trawling on the diets of common demersal fish by‐catch of a tropical prawn trawl fishery - Q. Dell; S. P. Griffiths; M. L. Tonks; W. A. Rochester; M. J. Miller; M. A. Duggan; T. D. van der Velde; R. D. Pillans; G. J. Coman; R. H. Bustamante; D. A. Milton (Journal of Fish Biology, 2013)
The ecological effect of prawn trawling on the benthos of the Gulf of Carpentaria, northern Australia, was investigated by examining stomach contents of common demersal fishes incidentally caught as by‐catch in the fishery. Fishes were collected from high and low fishing intensity sites in three regions based on vessel monitoring system data. The diets of eight species of benthic fish predators were compared between regions and fishing intensities. A regional effect on diet was evident for seven species. Only one generalist species had no significant difference in diet among the three regions. For the comparisons within each region, five predator species had significantly different diet between high and low fishing intensities in at least one region. Across the three regions, high fishing intensity sites had predators that consumed a greater biomass of crustaceans, molluscs and echinoderms. At low fishing intensity sites, predators had diets comprising a greater biomass of cnidarians and teleosts, and a different assemblage of molluscs, crustaceans and fishes. These changes in diet suggest that there may have been a shift in the structure of the benthic community following intensive fishing. Analysis of predator diets is a useful tool to help identify changes in the benthic community composition after exposure to fishing. This study also provided valuable diet information on a range of abundant generalist benthic predators to improve the ecosystem modelling tools needed to support ecosystem‐based fisheries management.

A possible role for mitochondrial dysfunction in migraine - S. Stuart; L. R. Griffiths (Molecular Genetics and Genomics, 2012)

IGS08: the IGS realization of ITRF2008 - P. Rebischung; J. Griffiths; J. Ray; R. Schmid; X. Collilieux; B. Garayt (GPS Solutions, 2012)

High doses of dextromethorphan, an NMDA antagonist, produce effects similar to classic hallucinogens - Chad J. Reissig; Lawrence P. Carter; Matthew W. Johnson; Miriam Z. Mintzer; Margaret A. Klinedinst; Roland R. Griffiths (Psychopharmacology, 2012)

Induction of antioxidative Nrf2 gene transcription by coffee in humans: depending on genotype? - Ute Boettler; Nadine Volz; Nicole Teller; Larisa M. Haupt; Tamara Bakuradze; Gerhard Eisenbrand; Gerhard Bytof; Ingo Lantz; Lyn R. Griffiths; Doris Marko (Molecular Biology Reports, 2012)

Comparison of genomic DNA extraction techniques from whole blood samples: a time, cost and quality evaluation study - Diego Chacon-Cortes; Larisa M. Haupt; Rod A. Lea; Lyn R. Griffiths (Molecular Biology Reports, 2012)

Development of an eight gene expression profile implicating human breast tumours of all grade - P. N. Gabrovska; R. A. Smith; T. Tiang; S. R. Weinstein; L. M. Haupt; L. R. Griffiths (Molecular Biology Reports, 2012)

Presence of Arundinaria gigantea (river cane) on numerous non-wetland sites suggests improper ecological classification of the species - Benjamin R. Tanner; David A. Kinner; Adam D. Griffith; Robert S. Young; Lee M. Sorrell (Wetlands Ecology and Management, 2011)

Psilocybin occasioned mystical-type experiences: immediate and persisting dose-related effects - Roland R. Griffiths; Matthew W. Johnson; William A. Richards; Brian D. Richards; Una McCann; Robert Jesse (Psychopharmacology, 2011)

Transport of NOX Emissions from Sugarcane Fertilisation into the Great Barrier Reef Lagoon - Clare Paton-Walsh; Stephen R. Wilson; Travis Naylor; David W. T. Griffith; O. T. Denmead (Environmental Modeling & Assessment, 2011)

Pharmacodynamic Model of Parathyroid Hormone Modulation by a Negative Allosteric Modulator of the Calcium-Sensing Receptor - Anson K. Abraham; Tristan S. Maurer; Amit S. Kalgutkar; Xiang Gao; Mei Li; David R. Healy; Donna N. Petersen; David A. Griffith; Donald E. Mager (The AAPS Journal, 2011)

Identification of molecular genetic factors that influence migraine - Bridget H. Maher; Lyn R. Griffiths (Molecular Genetics and Genomics, 2011)

Microsatellite standardization and evaluation of genotyping error in a large multi-partner research programme for conservation of Atlantic salmon (Salmo salar L.) - J. S. Ellis; J. Gilbey; A. Armstrong; T. Balstad; E. Cauwelier; C. Cherbonnel; S. Consuegra; J. Coughlan; T. F. Cross; W. Crozier; E. Dillane; D. Ensing; et al. (Genetica, 2011)

Effects of simultaneous climate change and geomorphic evolution on thermal characteristics of a shallow Alaskan lake - Jennifer R. Griffiths; Daniel E. Schindler; Laurie S. Balistrieri; Gregory T. Ruggerone (Limnology and Oceanography, 2011)
We used a hydrodynamics model to assess the consequences of climate warming and contemporary geomorphic evolution for thermal conditions in a large, shallow Alaskan lake. We evaluated the effects of both known climate and landscape change, including rapid outlet erosion and migration of the principal inlet stream, over the past 50 yr as well as future scenarios of geomorphic restoration. Compared to effects of air temperature during the past 50 yr, lake thermal properties showed little sensitivity to substantial (~60%) loss of lake volume, as the lake maximum depth declined from 6 m to 4 m driven by outlet erosion. The direction and magnitude of future lake thermal responses will be driven largely by the extent of inlet stream migration when it occurs simultaneously with outlet erosion. Maintaining connectivity with inlet streams had substantial effects on buffering lake thermal responses to warming climate. Failing to account for changing rates and types of geomorphic processes under continuing climate change may misidentify the primary drivers of lake thermal responses and reduce our ability to understand the consequences for aquatic organisms.

Benzonatate Ingestion Reported to the National Poison Center Database System (NPDS) - Mark L. Winter; Henry A. Spiller; Jill R. K. Griffith (Journal of Medical Toxicology, 2010)

Interspecific and conspecific colony mergers in the dwarf honey bees Apis andreniformis and A. florea - S. Wongvilas; S. Deowanish; J. Lim; V. R. D. Xie; O. W. Griffith; B. P. Oldroyd (Insectes Sociaux, 2010)

Effects of climate‐driven primary production change on marine food webs: implications for fisheries and conservation - C. J. BROWN; E. A. FULTON; A. J. HOBDAY; R. J. MATEAR; H. P. POSSINGHAM; C. BULMAN; V. CHRISTENSEN; R. E. FORREST; P. C. GEHRKE; N. A. GRIBBLE; S. P. GRIFFITHS; H. LOZANO‐MONTES; et al. (Global Change Biology, 2010)
Climate change is altering the rate and distribution of primary production in the world's oceans. Primary production is critical to maintaining biodiversity and supporting fishery catches, but predicting the response of populations to primary production change is complicated by predation and competition interactions. We simulated the effects of change in primary production on diverse marine ecosystems across a wide latitudinal range in Australia using the marine food web model Ecosim. We link models of primary production of lower trophic levels (phytoplankton and benthic producers) under climate change with Ecosim to predict changes in fishery catch, fishery value, biomass of animals of conservation interest, and indicators of community composition. Under a plausible climate change scenario, primary production will increase around Australia and generally this benefits fisheries catch and value and leads to increased biomass of threatened marine animals such as turtles and sharks. However, community composition is not strongly affected. Sensitivity analyses indicate overall positive linear responses of functional groups to primary production change. Responses are robust to the ecosystem type and the complexity of the model used. However, model formulations with more complex predation and competition interactions can reverse the expected responses for some species, resulting in catch declines for some fished species and localized declines of turtle and marine mammal populations under primary productivity increases. We conclude that climate‐driven primary production change needs to be considered by marine ecosystem managers and more specifically, that production increases can simultaneously benefit fisheries and conservation. Greater focus on incorporating predation and competition interactions into models will significantly improve the ability to identify species and industries most at risk from climate change.

Comparison of zooplankton vertical migration in an ice‐free and a seasonally ice‐covered Arctic fjord: An insight into the influence of sea ice cover on zooplankton behavior - Margaret I. Wallace; Finlo R. Cottier; Jørgen Berge; Geraint A. Tarling; Colin Griffiths; Andrew S. Brierley (Limnology and Oceanography, 2010)
We present observations of zooplankton diel vertical migration (DVM) over a period of 2 yr in an ice‐free and a seasonally ice‐covered Arctic fjord. The contrasting environments permitted assessment of the influences of physical and biological factors on temporal variability in DVM patterns and a test of the hypothesis that a reduction in summer sea ice extent and thickness following climatic warming will lead to changes in DVM via the loss of a shading effect on the pelagic marine environment. Acoustic backscatter and vertical velocity data from moored 300‐kHz acoustic Doppler current profilers were used to derive DVM patterns, while measurements of sea ice and snow thickness enabled assessment of the underwater light environment and consideration of its potential to influence DVM. Pronounced differences in DVM between the sites emerged during summertime when intermittent synchronized DVM was observed at the ice‐free site, whereas the ice‐covered site was characterized by asynchronous behavior, thereby highlighting the influence of sea ice. Notably, the 0.8‐m‐thick sea ice cover was deemed important for its influence on water column properties such as food, turbidity, and zooplankton species composition, as indicated by biological samples from moored sediment traps, rather than a simple shading of the ocean and direct modification of zooplankton DVM. Loss of Arctic sea ice is likely to have an indirect but substantial effect on zooplankton DVM via modification of hydrography and composition of the pelagic community.

Are European starlings breeding in the Azores archipelago genetically distinct from birds breeding in mainland Europe? - Verónica C. Neves; Kate Griffiths; Fiona R. Savory; Robert W. Furness; Barbara K. Mable (European Journal of Wildlife Research, 2010)

High levels of genetic divergence between Tasmanian and Victorian platypuses, Ornithorhynchus anatinus, as revealed by microsatellite loci - Elise Furlan; Paul A. Umina; Paul J. Mitrovski; Nick Gust; Josh Griffiths; Andrew R. Weeks (Conservation Genetics, 2010)

Amnestic effects of sodium oxybate are less than those of triazolam—reply to Drs. Zvosec and Smith - Lawrence P. Carter; Miriam Z. Mintzer; Roland R. Griffiths (Psychopharmacology, 2009)

Comparison of patterns of genetic variability in wild and supportively bred stocks of brown trout, Salmo trutta - A. M. GRIFFITHS; D. BRIGHT; J. R. STEVENS (Fisheries Management and Ecology, 2009)

Quantifying the metabolic cost to an Antarctic liverwort of responding to an abrupt increase in UVB radiation exposure - K. R. S. SNELL; T. KOKUBUN; H. GRIFFITHS; P. CONVEY; D. A. HODGSON; K. K. NEWSHAM (Global Change Biology, 2009)
We quantified the metabolic cost to the Antarctic leafy liverwort Cephaloziella varians of responding to an abrupt increase in ultraviolet B (UVB) radiation exposure in the natural environment at Rothera Point on the western Antarctic Peninsula (67 °34′S, 68 °07′W). The liverwort was protected from exposure to UVB radiation for 44 days with screens containing Mylar polyester, after which time its thalli, which are normally black in colour, had become green owing to reduced concentrations of an anthocyanidin, identified here as riccionidin A, in thallus tips. Thalli were then exposed to an abrupt increase in UVB radiation by removing the screens. The thalli became visibly darker within 48 h of the screens being removed, resynthesizing riccionidin A to the same concentration as that present in thalli outside screens during this period. Chlorophyll fluorescence measurements indicated that nonphotochemical quenching was higher in the thalli formerly under the screens than in those not previously covered with screens, but that F v / F m and photochemical quenching were the same in the two groups of thalli. We used data from aqueous phase oxygen electrode measurements to calculate an estimate for carbon fixation by C. varians during the 48 h after the screens were removed. Assuming a photosynthetic quotient for Antarctic bryophytes of 1, these analyses indicated that the minimum weight of carbon used to synthesize riccionidin A was equivalent to 1.85% of the carbon fixed by thalli during the 48 h after the abrupt increase in UVB radiation exposure.

Cognitive, psychomotor, and subjective effects of sodium oxybate and triazolam in healthy volunteers - Lawrence P. Carter; Roland R. Griffiths; Miriam Z. Mintzer (Psychopharmacology, 2009)

Caffeine withdrawal, acute effects, tolerance, and absence of net beneficial effects of chronic administration: cerebral blood flow velocity, quantitative EEG, and subjective effects - Stacey C. Sigmon; Ronald I. Herning; Warren Better; Jean L. Cadet; Roland R. Griffiths (Psychopharmacology, 2009)

Geographic patterns of non-carpeted floor dust loading in Syracuse, New York (USA) homes - D. L. Johnson; A. Hunt; D. A. Griffith; J. M. Hager; J. Brooks; H. StellaLevinsohn; A. Lanciki; R. Lucci; D. Prokhorova; S. L. Blount (Environmental Geochemistry and Health, 2009)

Complete mitochondrial control region sequences indicate a distinct variety of brown trout Salmo trutta in the Aral Sea - A. M. Griffiths; D. Bright; J. R. Stevens (Journal of Fish Biology, 2009)
Complete sequencing of the mtDNA control region (CR) from five specimens of brown trout Salmo trutta from the Amu Darya River identified two novel haplotypes belonging to the Danubian lineage. This finding supports the long‐standing hypothesis that brown trout in the Aral Sea represent a distinct genetic stock and also illustrates the benefits that complete sequencing of the CR can provide for elucidating phylogeographic relationships.

On the precision and accuracy of IGS orbits - Jake Griffiths; Jim R. Ray (Journal of Geodesy, 2009)

Genetic variation in strains of zebrafish (Danio rerio) and the implications for ecotoxicology studies - T. S. Coe; P. B. Hamilton; A. M. Griffiths; D. J. Hodgson; M. A. Wahab; C. R. Tyler (Ecotoxicology, 2009)

Linkage mapping of CVD risk traits in the isolated Norfolk Island population - C. Bellis; H. C. Cox; T. D. Dyer; J. C. Charlesworth; K. N. Begley; S. Quinlan; R. A. Lea; S. C. Heath; J. Blangero; L. R. Griffiths (Human Genetics, 2008)

Association of the GNAS locus with severe malaria - Sarah Auburn; Mahamadou Diakite; Andrew E. Fry; Anita Ghansah; Susana Campino; Anna Richardson; Muminatou Jallow; Fatou Sisay-Joof; Margaret Pinder; Michael J. Griffiths; Norbert Peshu; Thomas N. Williams; et al. (Human Genetics, 2008)

Homalanthus polyandrus (Euphorbiaceae) on Macauley Island, southern Kermadec Islands, with notes on that island's vascular flora - J. W. Barkla; P. J. Dilks; T. C. Greene; R. Griffiths (New Zealand Journal of Botany, 2008)
Homalanthus polyandrus (Kermadec poplar; Euphorbiaceae) is reported for Macauley Island, southern Kermadec Islands group. Previously this species had been reported (without a substantiating herbarium specimen) from that island by T. F. Cheeseman in 1887. In 2006 a single large tree was discovered on the western edge of the Macauley Island plateau. It is likely to have established following the eradication of feral goats in 1970 and may have arisen from bird‐dispersed seed from Raoul Island. The vegetation on Macauley Island has undergone a huge transition from a presumed earlier forested cover to the current Hypolepis dicksonioides fernland and Cyperus insularis sedgeland. A comprehensive list of all vascular plants recorded for Macauley Island is included in an appendix.

The role of pheromones in freshwater fishes - D. Burnard; R. E. Gozlan; S. W. Griffiths (Journal of Fish Biology, 2008)
The study of fish pheromones is particularly relevant because of the conserved nature of chemoreception in vertebrates. However, most fish pheromone systems remain unstudied. All the major known pheromones of freshwater fish and their associated behaviours were reviewed. Importantly, those studies that have demonstrated the connection between behaviour and pheromones in freshwater fishes have resulted in a wide range of applications in management. For example, pheromones released by the sea lamprey Petromyzon marinus have a practical function in pheromone traps, showing how chemical communication can be used in the management of invasive species. Future research on fish pheromones should include olfactory systems in a wider range of species testing the possibility that a few distinct models could be applied to the all fishes. Progress in research on fish pheromones should include a closer collaboration with other research fields such as evolutionary biology to allow a better understanding of fish pheromones systems divergence and mate selection where correlation between phenotypic dominance and pheromone production is still largely ignored. Finally, the example of pheromone interaction between an invasive species topmouth gudgeon Pseudorasbora parva and a native endangered species sunbleak Leucaspius delineatus is provided to illustrate the concept of pheromone pollution that assists its establishment in a novel ecosystem.

Implications of life history for genetic structure and migration rates of southern African coastal invertebrates: planktonic, abbreviated and direct development - P. R. Teske; I. Papadopoulos; G. I. Zardi; C. D. McQuaid; M. T. Edkins; C. L. Griffiths; N. P. Barker (Marine Biology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Exploration of Ellsworth Subglacial Lake: a concept paper on the development, organisation and execution of an experiment to explore, measure and sample the environment of a West Antarctic subglacial lake - M.J. Siegert; A. Behar; M. Bentley; D. Blake; S. Bowden; P. Christoffersen; C. Cockell; H. Corr; D. C. Cullen; H. Edwards; A. Ellery; C. Ellis-Evans; et al. (Reviews in Environmental Science and Bio/Technology, 2007)

Campylobacter lari : genotype and antibiotic resistance of isolates from cattle, wildlife and water in an area of mixed dairy farmland in the United Kingdom - A. J. H. Leatherbarrow; R. Griffiths; C. A. Hart; R. Kemp; N. J. Williams; P. J. Diggle; E. J. Wright; J. Sutherst; P. Houghton; N. P. French (Environmental Microbiology, 2007)
Summary Campylobacter lari is a rare human pathogen most commonly associated with birds and shellfish. Little information has been published regarding its prevalence in other environments, or on its potential role as a reservoir of antibiotic resistance. In this study, we characterized 109 C. lari isolated from a range of hosts using pulsed‐field gel electrophoresis of macro‐restricted chromosomal DNA, and by determining their susceptibility to a panel of four antibiotics. Pulsed‐field gel electrophoresis analysis showed C. lari to be genetically diverse, particularly in isolates from wild birds and environmental water. The most common composite macro‐restriction profile (cMRP) was found in multiple hosts (cattle, badgers, wild birds and rabbits), and seven other cMRPs were recovered from more than one host. All isolates were resistant to nalidixic acid and ciprofloxacin. Resistance to erythromycin and ampicillin was uncommon, but was observed in isolates from wild birds, cattle, wild mammals and water samples. The presence of the same cMRP in multiple hosts provides further evidence of transmission between livestock, wildlife and the environment, or for a common source of infection.

A triazolam/amphetamine dose–effect interaction study: dissociation of effects on memory versus arousal - Miriam Z. Mintzer; Roland R. Griffiths (Psychopharmacology, 2007)

Toward a plant‐based proxy for the isotope ratio of atmospheric water vapor - BRENT R. HELLIKER; HOWARD GRIFFITHS (Global Change Biology, 2007)
Atmospheric water vapor is a major component of the global hydrological cycle, but the isotopic balance of vapor is largely unknown. Here, using models and observations, we show that the leaf water δ 18 O in the tropical Crassulacean acid metabolism (CAM) epiphyte Tillandsia usneoides is controlled by the δ 18 O of atmospheric water vapor in a predictable manner, irrespective of precipitation inputs. By taking the leaf‐water‐atmospheric signature as recorded in plant organic material, we have reconstructed the atmospheric water vapor δ 18 O signature for Miami, FL, USA between 1878 and 2005 using contemporary and herbarium specimens. T. usneoides ranges from Virginia, USA southwards through the tropics to Argentina, and the CAM epiphytic lifeform is widespread in other species. Therefore, there is significant potential for using epiphytes to reconstruct the isotope ratio of atmospheric water (both δ 18 O and δ D) for spatial scales that span over 60° of latitude and temporal scales that cover the last century of global temperature increase.

Toward a plant-based proxy for the isotope ratio of atmospheric water vapor - BRENT R. HELLIKER; HOWARD GRIFFITHS (Global Change Biology, 2007)

Impaired hatching success and male-biased embryo mortality in Tree Sparrows - Magnus Svensson; Pekka T. Rintamäki; Tim R. Birkhead; Simon C. Griffith; Arne Lundberg (Journal of Ornithology, 2007)

Crop pathogens and other Fusarium species associated with Austrostipa aristiglumis - A. R. Bentley; T. Petrovic; S. P. Griffiths; L. W. Burgess; B. A. Summerell (Australasian Plant Pathology, 2007)

Chronic intragastric administration of gamma-butyrolactone produces physical dependence in baboons - Amy K. Goodwin; Roland R. Griffiths; P. Rand Brown; Wolfgang Froestl; Cornelis Jakobs; K. Michael Gibson; Elise M. Weerts (Psychopharmacology, 2006)

Dose effects of triazolam on brain activity during episodic memory encoding: a PET study - Miriam Z. Mintzer; Hiroto Kuwabara; Mohab Alexander; James R. Brasic; Weiguo Ye; Monique Ernst; Roland R. Griffiths; Dean F. Wong (Psychopharmacology, 2006)

Psilocybin can occasion mystical-type experiences having substantial and sustained personal meaning and spiritual significance - R. R. Griffiths; W. A. Richards; U. McCann; R. Jesse (Psychopharmacology, 2006)

A freshwater‐feeding Lampetra fluviatilis L. population in Lough Neagh, Northern Ireland - C. E. Goodwin; D. Griffiths; J. T. A. Dick; R. W. Elwood (Journal of Fish Biology, 2006)
Pollan Coregonus autumnalis , caught in the fresh waters of Lough Neagh, Northern Ireland, were scarred by river lamprey Lampetra fluviatilis and adult river lamprey were found for much of the year with full guts, indicating a freshwater‐feeding population.

C-reactive protein mediates CD11b expression in monocytes through the non-receptor tyrosine kinase, Syk, and calcium mobilization but not through cytosolic peroxides - K. J. Woollard; C. Fisch; R. Newby; H. R. Griffiths (Inflammation Research, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Low gene flow but high genetic diversity in the threatened Mallorcan midwife toad Alytes muletensis - F. J. L. KRAAIJEVELD‐SMIT; T. J. C. BEEBEE; R. A. GRIFFITHS; R. D. MOORE; L. SCHLEY (Molecular Ecology, 2005)
We investigated fine‐scale genetic structuring in the rare and vulnerable Mallorcan midwife toad Alytes muletensis using eight polymorphic microsatellite markers. The current range of this amphibian is restricted to some 19 sites of which six are derived from reintroductions, all located in the mountain ranges of Mallorca. We sampled tadpoles from 14 pools covering 10 natural sites and two reintroduction sites for microsatellite DNA analyses. Relatively high levels of genetic variation were found in most pools ( H E = 0.38–0.71, allelic richness = 2.6–6.2). Only at one pool has the population recently gone through a bottleneck. Dispersal between pools in different torrents does not occur whereas downstream dispersal between pools within the same torrent does happen at low frequencies. This occasional exchange of individuals does not lead to neighbouring pools in the same torrent being panmictic. This can be concluded because all F ST values (0.12–0.53) differ significantly from zero and structure analyses identified neighbouring pools as separate populations. Furthermore, assignment and migration tests showed little exchange between neighbouring pools. If upstream locations or complete torrents go extinct, they are unlikely to be recolonized naturally. For conservation purposes, reintroductions of tadpoles to sites where local extinctions have occurred may therefore be advisable.

Change in mean temperature as a predictor of extreme temperature change in the Asia–Pacific region - G. M. Griffiths; L. E. Chambers; M. R. Haylock; M. J. Manton; N. Nicholls; H.‐J. Baek; Y. Choi; P. M. Della‐Marta; A. Gosai; N. Iga; R. Lata; V. Laurent; et al. (International Journal of Climatology, 2005)
Trends (1961–2003) in daily maximum and minimum temperatures, extremes and variance were found to be spatially coherent across the Asia–Pacific region. The majority of stations exhibited significant trends: increases in mean maximum and mean minimum temperature, decreases in cold nights and cool days, and increases in warm nights. No station showed a significant increase in cold days or cold nights, but a few sites showed significant decreases in hot days and warm nights. Significant decreases were observed in both maximum and minimum temperature standard deviation in China, Korea and some stations in Japan (probably reflecting urbanization effects), but also for some Thailand and coastal Australian sites. The South Pacific convergence zone (SPCZ) region between Fiji and the Solomon Islands showed a significant increase in maximum temperature variability. Correlations between mean temperature and the frequency of extreme temperatures were strongest in the tropical Pacific Ocean from French Polynesia to Papua New Guinea, Malaysia, the Philippines, Thailand and southern Japan. Correlations were weaker at continental or higher latitude locations, which may partly reflect urbanization. For non‐urban stations, the dominant distribution change for both maximum and minimum temperature involved a change in the mean, impacting on one or both extremes, with no change in standard deviation. This occurred from French Polynesia to Papua New Guinea (except for maximum temperature changes near the SPCZ), in Malaysia, the Philippines, and several outlying Japanese islands. For urbanized stations the dominant change was a change in the mean and variance, impacting on one or both extremes. This result was particularly evident for minimum temperature. The results presented here, for non‐urban tropical and maritime locations in the Asia–Pacific region, support the hypothesis that changes in mean temperature may be used to predict changes in extreme temperatures. At urbanized or higher latitude locations, changes in variance should be incorporated. Copyright © 2005 Royal Meteorological Society.

Spontaneous and precipitated withdrawal after chronic intragastric administration of gamma-hydroxybutyrate (GHB) in baboons - Elise M. Weerts; Amy K. Goodwin; Roland R. Griffiths; P. Rand Brown; Wolfgang Froestl; Cornelis Jakobs; K. Michael Gibson (Psychopharmacology, 2005)

Economic issues in the management of plants invading natural environments: Scotch broom in Barrington Tops National Park - Doreen Odom; J. A. Sinden; Oscar Cacho; G. R. Griffith (Biological Invasions, 2005)

Characterisation of a barley (Hordeum vulgare L.) homologue of the Arabidopsis flowering time regulator GIGANTEA - R. P. Dunford; S. Griffiths; V. Christodoulou; D. A. Laurie (Theoretical and Applied Genetics, 2005)

Flumazenil-precipitated withdrawal in healthy volunteers following repeated diazepam exposure - Miriam Z. Mintzer; Roland R. Griffiths (Psychopharmacology, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

A critical review of caffeine withdrawal: empirical validation of symptoms and signs, incidence, severity, and associated features - Laura M. Juliano; Roland R. Griffiths (Psychopharmacology, 2004)

Landscape Trends in Mid-Atlantic and Southeastern United States Ecoregions - Jerry A. Griffith; Stephen V. Stehman; Thomas R. Loveland (Environmental Management, 2003)

Effects of Intertidal Elevation on the Rockpool Ichthyofaunas of Temperate Australia - Shane P. Griffiths; Ron J. West; Andy R. Davis (Environmental Biology of Fishes, 2003)

Sex‐specific survival and parasitism in three‐spined sticklebacks: seasonal patterns revealed by molecular analysis - K. E. Arnold; A. Adam; K. J. Orr; R. Griffiths; I. Barber (Journal of Fish Biology, 2003)
A molecular method of identifying sex in three‐spined sticklebacks Gasterosteus aculeatus showed that adult males had a higher prevalence of dermal Glugea anomala cysts than adult females, and young‐of‐the‐year had more than adults. At the end of the breeding season, as predicted, the adult sex ratio became female biased and there was a disproportionate increase in G. anomala parasitism in adult males.

Prospects for whole genome linkage disequilibrium mapping in domestic dog breeds - Changbaig Hyun; Lucio J. Filippich; Rod A. Lea; Graeme Shepherd; Ian P. Hughes; Lyn R. Griffiths (Mammalian Genome, 2003)

Construction and characterisation of a hexaploid wheat (Triticum aestivum L.) BAC library from the reference germplasm ‘Chinese Spring’ - S. Allouis; G. Moore; A. Bellec; R. Sharp; P. Faivre Rampant; K. Mortimer; S. Pateyron; T. N. Foote; S. Griffiths; M. Caboche; B. Chalhoub (Cereal Research Communications, 2003)

The adenosine receptor antagonist CGS15943 reinstates cocaine-seeking behavior and maintains self-administration in baboons - Elise M. Weerts; Roland R. Griffiths (Psychopharmacology, 2003)

Effects of α-difluoromethylornithine on local recurrence and pulmonary metastasis from MDA-MB-435 breast cancer xenografts in nude mice - Andrea Manni; Sharlene Washington; Laura Craig; Michael Cloud; James W. Griffith; Michael F. Verderame; Lindsay J. Texter; David Mauger; Laurence M. Demers; John F. Harms; Danny R. Welch (Clinical & Experimental Metastasis, 2003)

Development and Evaluation of a Macroinvertebrate Biotic Integrity Index (MBII) for Regionally Assessing Mid-Atlantic Highlands Streams - DONALD J. KLEMM; KAREN A. BLOCKSOM; FLORENCE A. FULK; ALAN T. HERLIHY; ROBERT M. HUGHES; PHILIP R. KAUFMANN; DAVID V. PECK; JOHN L. STODDARD; WILLIAM T. THOENY; MICHAEL B. GRIFFITH; WAYNE S. DAVIS (Environmental Management, 2003)

Analysis of Macroinvertebrate Assemblages in Relation to Environmental Gradients among Lotic Habitats of California's Central Valley - Michael B. Griffith; Peter Husby; Robert K. Hall; Philip R. Kaufmann; Brian H. Hill (Environmental Monitoring and Assessment, 2003)

Eight microsatellite loci in the Caribbean lizard, Anolis roquet - R. Ogden; T.J. Griffiths; R.S. Thorpe (Conservation Genetics, 2002)

Nonsyndromic recessive deafness DFNB18 and Usher syndrome type IC are allelic mutations of USHIC - Zubair M. Ahmed; Tenesha N. Smith; Saima Riazuddin; Tomoko Makishima; Manju Ghosh; Sirosh Bokhari; Puthezhath S. Menon; Dilip Deshmukh; Andrew J. Griffith; Sheikh Riazuddin; Thomas B. Friedman; Edward R. Wilcox (Human Genetics, 2002)

A technique for the molecular genetic analysis of Daphnia resting eggs from sub-recent lake sediments - Vicky A. Reid; Gary R. Carvalho; D. Glen George; Huw I. Griffiths (Journal of Paleolimnology, 2002)

Population dynamics of reintroduced forest birds on New Zealand islands - Doug P. Armstrong; R. Scott Davidson; Wendy J. Dimond; John K. Perrott; Isabel Castro; John G. Ewen; Richard Griffiths; Jason Taylor (Journal of Biogeography, 2002)
Aim We studied dynamics of four populations of New Zealand forest birds for 5–9 years after reintroduction to islands. We primarily aimed to predict whether these populations were viable, and what, if any, management was needed to maintain them. However, the small scale of these islands also provided an opportunity to study density‐dependent population growth over a short time frame. Location We studied New Zealand robin (toutouwai, Petroica australis ) and stitchbird (hihi, Notiomystis cincta ) populations reintroduced to Tiritiri Matangi, a 220‐ha offshore island near Auckland, and saddleback (tieke, Philesturnus carunculatus ) and stitchbird populations reintroduced to Mokoia, a 135‐ha island in Lake Rotorua. These islands are free of mammalian predators, but have highly modified habitat following clearing and regeneration. Methods We closely monitored each population, individually marking all or most of the birds and in some cases experimentally manipulated population density or food supply. We used model selection procedures to understand factors affecting survival, fecundity and dispersal, and developed stochastic simulation models. Results The Tiritiri Matangi robin and Mokoia saddleback populations grew without management and appear to be viable. Both showed strong evidence of density‐dependent growth, with fecundity (saddlebacks) and juvenile survival (both populations) declining with increasing density. Neither stitchbird population appears viable without management and supplementation experiments showed reproduction and/or survival to be limited by food supply. The Tiritiri Matangi population appears viable as long as supplementary feeding continues. However, the Mokoia population has a high mortality rate regardless of supplementary feeding, resulting in tenuous viability even with intensive management. Mokoia stitchbirds suffer from infection by Aspergillus fumigatus , a pathogenic fungus that is prevalent in highly modified habitats and more abundant on Mokoia than Tiritiri Matangi. Main conclusions Some forest birds can thrive in regenerating forest on islands and strong evidence of density dependence can be detected in such populations in as little as 5 years. This allows density‐dependent models to be developed, providing guidance when island populations are harvested for further translocations. Other species are limited by food supply in regenerating environments, a problem potentially overcome by management. However, prevalence of A. fumigatus may render highly modified environments uninhabitable by some species regardless of management.

Influence of polyamines on in vitro and in vivo features of aggressive and metastatic behavior by human breast cancer cells - Andrea Manni; Sharlene Washington; James W. Griffith; Michael F. Verderame; David Mauger; Laurence M. Demers; Rajeev S. Samant; Danny R. Welch (Clinical & Experimental Metastasis, 2002)

New drugs for the treatment of inflammatory, respiratory and immunological diseases - R. Griffiths; K. Koch (Inflammation Research, 2002)

Authors response to: Critique of "Chromosome 17 and inducible nitric oxide synthase gene in human essential hypertension" by Rutherford et al. in Human Genetics published on-line September 2001 - Lyn R. Griffiths (Human Genetics, 2002)

Alcohol and false recognition: a dose-effect study - Miriam Z. Mintzer; Roland R. Griffiths (Psychopharmacology, 2001)

The Irish pollan, Coregonus autumnalis : options for its conservation - C. Harrod; D. Griffiths; T. K. McCarthy; R. Rosell (Journal of Fish Biology, 2001)
The ecology of four relict Irish populations of pollan ( Coregonus autumnalis ) is compared with that of the species elsewhere, and used to advocate conservation. The threats to these populations from introduced/invasive species, habitat degradation, climate warming and commercial exploitation are summarized and the legislation governing conservation of the stocks is reviewed. Conservation options (legislation, habitat restoration, stock translocation and stock augmentation) are outlined and their practicality and efficacy considered. A preliminary search indicates that there are a number of lakes that appear to be suitable for pollan translocation.

Relationship Between Antifreeze Protein and Freezing Resistance in Pseudomonas putida GR12-2 - Hidehisa Kawahara; Jiping Li; Marilyn Griffith; Bernard R. Glick (Current Microbiology, 2001)

Chromosome 17 and the inducible nitric oxide synthase gene in human essential hypertension - Sue Rutherford; Matthew P. Johnson; Robert P. Curtain; Lyn R. Griffiths (Human Genetics, 2001)

Production and transport of denitrification gases in shallow ground water - R. Well; J. Augustin; J. Davis; S.M. Griffith; K. Meyer; D.D. Myrold (Nutrient Cycling in Agroecosystems, 2001)

Historical biogeography and Late Quaternary environmental change of Lake Pamvotis, Ioannina (north‐western Greece): evidence from ostracods - Michael R. Frogley; Huw I. Griffiths; Timothy H. E. Heaton (Journal of Biogeography, 2001)
Aim The purpose of this study is to (1) investigate the Quaternary history of Lake Pamvotis using fossil ostracod faunal and isotopic analyses, and (2) use this fossil evidence to assess the pedigree of the lake's fauna and place it within a regional palaeobiogeographical context. Location Lake Pamvotis, situated in the Ioannina Basin, north‐western Greece. Methods Fossil samples were recovered from a 319 m‐long, 500 ka core drilled on the eastern shore of the current lake. Stable isotopic analyses were carried out on ostracod shell calcite. Results A total of 17 ostracod taxa were recovered, of which 13 occur in the modern lake. Fossil assemblages and corresponding isotopic profiles from the Last (Eemian) Interglacial and Last Glacial‐Holocene transition are presented and compared with modern‐day data. Some taxa (e.g. Leptocythere sp. A) appear to be lake basin endemics. Main conclusions The ostracod fauna is typical of temperate, carbonate‐rich standing waters and includes both European and Balkan endemic elements. The fossil fauna, coupled with the isotopic data, provides evidence for past lake‐level change, including a progressive deepening throughout much of the Last Interglacial and a gradual shallowing throughout the subsequent glacial. This culminated in a distinct interval of low lake‐levels at the height of the last glaciation. The Lateglacial witnessed a partial recovery in lake depth, although shallowing occurred once again during the Holocene. The biogeographical affinities of the ostracod fauna, whilst not unequivocal, nevertheless suggest that speciation in the region has been by vicariance and hydrological isolation, probably within the Pleistocene.

Reinforcing effects of oral cocaine: contextual determinants - Hendrée E. Jones; Bridgette E. Garrett; Roland R. Griffiths (Psychopharmacology, 2001)

Acute dose-effects of scopolamine on false recognition - Miriam Z. Mintzer; Roland R. Griffiths (Psychopharmacology, 2001)

Poster Session - J. van S. Graver; H. J. Banks; A. K. Sharp; A. Contessi; N. Baldassari; M. Maggioli; Sabine Prozell; Ch. Reichmuth; Maria Otília Carvalho; Ana Paula Pereira; A. Mexia; Sylvia Allen; et al. (Phytoparasitica, 2001)

Development of STS markers closely linked to the Ppd-H1 photoperiod response gene of barley (Hordeum vulgare L.) - L. Decousset; S. Griffiths; R. P. Dunford; N. Pratchett; D. A. Laurie (Theoretical and Applied Genetics, 2000)

DNA sex identification in the three‐spined stickleback - R. Griffiths; K. L. Orr; A. Adam; I. Barber (Journal of Fish Biology, 2000)
Two sex linked DNA markers are isolated in the three‐spined stickleback Gasterosteus aculeatus and a sex identification test is developed.

Infrequency of Pulmonary Microbial Colonisation Prior to Respiratory Disease in HIV-Infected Individuals - M. C. I. Lipman; S. Ainscough; P. D. Griffiths; M. A. Johnson; C. C. Kibbler; A. R. S. Deery (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Verifying Inventory Predictions of Animal Methane Emissions with Meteorological Measurements - O. T. Denmead; R. Leuning; D. W. T. Griffith; I. M. Jamie; M. B. Esler; L. A. Harper; J. R. Freney (Boundary-Layer Meteorology, 2000)

Familial typical migraine: significant linkage and localization of a gene to Xq24-28 - Dale R. Nyholt; Robert P. Curtain; Lyn R. Griffiths (Human Genetics, 2000)

Familial typical migraine: significant linkage and localization of a gene to Xq24–28 - Dale R. Nyholt; Robert P. Curtain; Lyn R. Griffiths (Human Genetics, 2000)

Caffeine withdrawal increases cerebral blood flow velocity and alters quantitative electroencephalography (EEG) activity - H. E. Jones; R. I. Herning; J. L. Cadet; R. R. Griffiths (Psychopharmacology, 2000)

A controlled study of flumazenil-precipitated withdrawal in chronic low-dose benzodiazepine users - M. Z. Mintzer; K. B. Stoller; R. R. Griffiths (Psychopharmacology, 1999)

Preliminary assessment of shallow water fish in three small intermittently open estuaries in southeastern Australia - S. P. GRIFFITHS; R. J. WEST (Fisheries Management and Ecology, 1999)
Small and juvenile fish from three intermittently open estuaries in south‐eastern Australia were sampled with a seine net to investigate species richness and the effect of estuary openings on assemblages. A total of 7285 fish were captured, representing 29 species. The most numerous fish were hardyhead, Atherinosoma microstoma Günther, flathead gudgeon, Philypnodon grandiceps Krefft, and non‐native mosquito fish, Gambusia holbrooki Girard. Economic species included sand whiting, Sillago ciliata Cuvier, and sand mullet, Myxus elongatus Günther. Significant differences in the numbers of species and the numbers of individuals were found between estuaries, but were not observed for individual estuaries before and after opening. However, fish assemblages changed after opening, with several species recruiting from the ocean. Small, intermittently open estuaries present a complex management problem. These waterbodies are easily degraded in terms of water quality and sedimentation, and are often opened mechanically as a result of flooding or health concerns. The importance of these areas as fish habitats and the recorded changes in fish assemblages after opening suggest that careful management is required, including improved assessment of the impact of entrance manipulation.

Identification of a new quantitative trait locus on Chromosome 7 controlling disease severity of collagen-induced arthritis in rats - Svetlana V. Dracheva; Elaine F. Remmers; Pércio S. Gulko; Yutaka Kawahito; Ryan E. Longman; Van R. Reese; Grant W. Cannon; Marie M. Griffiths; R. L. Wilder (Immunogenetics, 1999)

Zaleplon and triazolam in humans: acute behavioral effects and abuse potential - C. R. Rush; J. M. Frey; R. R. Griffiths (Psychopharmacology, 1999)

Synthesis of hydroxamic acids using SynPhase™ crowns: Development of the hydroxylamine trityl linker - Nicholas J. Ede; Ian W. James; Beata M. Krywult; Rachael M. Griffiths; Susan N. Eagle; Ben Gubbins; Jeffrey A. Leitch; Wayne R. Sampson; Andrew M. Bray (International Journal of Peptide Research and Therapeutics, 1999)

Triazolam and zolpidem: effects on human memory and attentional processes - M. Z. Mintzer; Roland R. Griffiths (Psychopharmacology, 1999)

A genetic linkage map of rat Chromosome 15 derived from five F 2 crosses - Jennifer S. Shepard; Elaine F. Remmers; Stephen Chen; Lisa Chang; Yutaka Kawahito; Pércio S. Gulko; Bina Joe; Ryan E. Longman; Svetlana Dracheva; Lynn Ge; Jianping Wang; Van R. Reese; et al. (Mammalian Genome, 1999)

Influence of Increasing Herbivore Pressure on Modification of Glucosinolate Content of Swedes (Brassica napus spp. rapifera) - R. J. Hopkins; D. W. Griffiths; A. N. E. Birch; R. G. McKinlay (Journal of Chemical Ecology, 1998)

Genetic differentiation among local populations of the European hedgehog ( Erinaceus europaeus ) in mosaic habitats - S. A. BECHER; R. GRIFFITHS (Molecular Ecology, 1998)
Tissue samples from 160 European hedgehogs, Erinaceus europaeus , representing eight small populations from a highly fragmented landscape in Oxfordshire, UK, were screened for polymorphism at six microsatellite loci. Permutation analysis of allelic compositions revealed no evidence for linkage disequilibrium among loci. Genotype proportions within populations and at five loci did not differ from those expected at Hardy–Weinberg equilibrium. However, significant heterozygote deficit and amplification failure of several samples necessitated removal of one locus from the analysis. Mean observed heterozygosity was 0.70. Average Rho ST was 0.079 and differed significantly from zero, suggesting restricted gene flow among local populations. Pairwise Nm values and geographical distance were not correlated, indicating that factors other than distance affected dispersal.

A genetic linkage map of rat chromosome 20 derived from five F 2 crosses - Y. Kawahito; Elaine F. Remmers; R. L. Wilder; Ryan E. Longman; Pércio S. Gulko; Jianping Wang; Stephen Chen; Lisa Chang; V. R. Reese; Svetlana Dracheva; Lynn Ge; Jean H. Hoffman; et al. (Immunogenetics, 1998)

Physical dependence increases the relative reinforcing effects of caffeine versus placebo - B. E. Garrett; R. R. Griffiths (Psychopharmacology, 1998)

Buspirone is differentiated from diazepam in humans using a three-response drug discrimination procedure - J. M. Frey; Miriam Z. Mintzer; C. R. Rush; R. R. Griffiths (Psychopharmacology, 1998)

Stable low-rate midazolam self-injection with concurrent physical dependence under conditions of long-term continuous availability in baboons - E. M. Weerts; Barbara J. Kaminski; Roland R. Griffiths (Psychopharmacology, 1998)

Analgesic activity of 2-amino-4-methylpyridine, a novel NO synthase inhibitor - E. R. Pettipher; T. A. Hibbs; M. A. Smith; R. J. Griffiths (Inflammation Research, 1997)

Benzodiazepine self-administration in humans and laboratory animals - implications for problems of long-term use and abuse - Roland R. Griffiths; Elise M. Weerts (Psychopharmacology, 1997)

Characterisation of Escherichia coli K-12 mutants defective in formate-dependent nitrite reduction: essential roles for hemN and the menFDBCE operon - K. Tyson; R. Metheringham; L. Griffiths; J. Cole (Archives of Microbiology, 1997)

Inflammation Research Association Meeting: The Puzzle Posed by Cytokines Lacking a Signal Sequence, New York Academy of Sciences, USA, 22 May 1997 - R. J. Griffiths; C. Gabel (Inflammation Research, 1997)

British Inflammation Research Association Meeting: Metalloproteinases and Inflammatory Diseases, The Fielder Centre, Hatfield, UK, 18 April 1997 - R. J. Griffiths; G. A. Bottomley (Inflammation Research, 1997)

Application of an augmented nitrification assay to elucidate the effects of a spring barley crop and manures on temporal variations in rates - R. E. Wheatley; K. Ritz; B. S. Griffiths (Biology and Fertility of Soils, 1997)

Effects of animal manure application and crop plants upon size and activity of soil microbial biomass under organically grown spring barley - K. Ritz; R. E. Wheatley; B. S. Griffiths (Biology and Fertility of Soils, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

Middle Pleistocene deposits at Frog Hall Pit, Stretton‐on-Dunsmore, Warwickshire, English Midlands, and their implications for the age of the type Wolstonian - D. H. Keen; G. R. Coope; R. L. Jones; M. H. Field; H. I. Griffiths; S. G. Lewis; D. Q. Bowen (Journal of Quaternary Science, 1997)

Middle Pleistocene deposits at Frog Hall Pit, Stretton-on-Dunsmore, Warwickshire, English Midlands, and their implications for the age of the type Wolstonian - D. H. Keen; G. R. Coope; R. L. Jones; M. H. Field; H. I. Griffiths; S. G. Lewis; D. Q. Bowen (Journal of Quaternary Science, 1997)

Caffeine reinforcement: the role of withdrawal - K. J. Schuh; R. R. Griffiths (Psychopharmacology, 1997)

Chemistry and microbial activity of forest and pasture riparian-zone soils along three Pacific Northwest streams - Robert P. Griffiths; James A. Entry; Elaine R. Ingham; William H. Emmingham (Plant and Soil, 1997)

Leaf Surface Compounds and Oviposition Preference of Turnip Root Fly Delia floralis: The Role of Glucosinolate and Nonglucosinolate Compounds - R. J. Hopkins; A. N. E. Birch; D. W. Griffiths; R. Baur; E. Städler; R. G. Mckinlay (Journal of Chemical Ecology, 1997)

A gene tree for β-globin sequences from melanesia - R. M. Harding; S. M. Fullerton; R. C. Griffiths; J. B. Clegg (Journal of Molecular Evolution, 1997)

Isolation and characterization of six polymorphic microsatellite loci in the European hedgehog Erinaceus europaeus - S. A. Becher; R. Griffiths (Molecular Ecology, 1997)

Biology and host specificity ofPlatphalonidia mystica (Lep.: Cochylidae) introduced into queensland to biologically controlParthenium hysterophorus (Asteraceae) - M. W. Griffiths; R. E. McFadyen (BioControl, 1993)

Immunoblot analysis of the humoral immune response to cytomegalovirus in non-pregnant and pregnant guinea pigs - F. R. Bu; Brigitte P. Griffith (Archives of Virology, 1990)

Properties of the phosphate and phosphite transport systems of Phytophthora palmivora - Julia M. Griffith; Louise A. Akins; Bruce R. Grant (Archives of Microbiology, 1989)

Effect of phosphate on the toxicity of phosphite in Phytophthora palmivora - Julia M. Griffith; Robert H. Smillie; Julie O. Niere; Bruce R. Grant (Archives of Microbiology, 1989)

Calcium control of differentiation in Phytophthora palmivora - Julia M. Griffith; Joanne R. Iser; Bruce R. Grant (Archives of Microbiology, 1988)

Persistence of high titre antibodies to the early antigens of cytomegalovirus in pregnant women - P. D. Griffiths; K. J. Buie; R. B. Heath (Archives of Virology, 1980)

Inhibition of glutethimide absorption - Yukiyoshi Kamisaka; D. William Griffiths; Leslie Leduc; Milton Lipsky; Horace Martin; Walter R. Thayer (Archives of Toxicology, 1972)